Polarizing plate and organic electroluminescence display device

By using polarizers containing low binary spectroscopic materials in organic EL display equipment and adopting a direct contact structure, the problem of decreasing black tightness in the equipment in high temperature environment is solved, and good image quality and reflectivity control is achieved.

JP2025066128APending Publication Date: 2025-04-22FUJIFILM CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2025009107
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-09-09
Filing Date
2025-01-22
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The prior art is difficult to maintain the front-direction black tightness of the organic EL display device after long exposure in high temperature environments, resulting in changes in black color and increased reflectivity.

Method used

A polarizer consisting of a first liquid crystal compound and a bispectral material is adopted. The bispectral material content of the polarizer is less than 40% of the total mass of the polarizer, and by adjusting the contact between the polarizer and the optical opposite-sex layer, it is directly contacted without a glue layer to reduce light reflection.

Benefits of technology

After long exposure in high temperature environments, the polarizer can maintain good front-direction black tightness, reduce black color changes and reflectivity, and improve the image quality of the display device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025066128000030
    Figure 2025066128000030
  • Figure 2025066128000031
    Figure 2025066128000031
  • Figure 2025066128000032
    Figure 2025066128000032
Patent Text Reader

Abstract

To provide a polarizing plate and an organic EL display device, wherein even after the organic EL display device obtained by bonding the polarizing plate to an organic EL display panel is exposed to a high-temperature environment for a long time, blackness in the front direction is excellent.SOLUTION: A polarizing plate includes: a polarizer formed using a composition containing a first liquid crystal compound and a dichroic substance; and an optical anisotropic layer formed using a composition containing a second liquid crystal compound and disposed adjacent to the polarizer. The content of dichroic substance in the polarizer is 40 mass% or less of the total mass of the polarizer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polarizing plate and an organic electroluminescent display device. [Background technology]

[0002] Optically anisotropic layers having phase difference are used in a wide variety of applications. For example, organic electroluminescence (EL) display devices have a structure using metal electrodes, which may cause problems of contrast reduction and glare due to reflection of external light. Therefore, a polarizing plate including an optically anisotropic layer and a polarizer has been used in the past to suppress the adverse effects of external light reflection. Patent Document 1 discloses a circular polarizing plate in which a retardation layer (optically anisotropic layer) is attached to a polarizer formed using a dichroic material via a pressure-sensitive adhesive layer. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-023153 A Summary of the Invention [Problem to be solved by the invention]

[0004] On the other hand, in recent years, organic EL display devices are required to have excellent tight black when viewed from the front in order to further improve image quality. In particular, organic EL display devices are required to have excellent tight black when viewed from the front even after being exposed to a high-temperature environment for a long period of time. Here, tight black means that when the image display device displays black, the black coloring is suppressed and the reflectance of reflected light is low.

[0005] The present inventors prepared a circular polarizing plate by bonding a polarizer and an optically anisotropic layer via an adhesive layer as disclosed in Patent Document 1, attached the plate to an organic EL display panel, and evaluated the performance of the resulting organic EL display device after exposing it to a high-temperature environment for a long period of time. As a result, they found that the above-mentioned demands were not fully met.

[0006] In view of the above-mentioned circumstances, an object of the present invention is to provide a polarizing plate that exhibits excellent black density in the front direction even after an organic EL display device obtained by attaching the polarizing plate to an organic EL display panel is exposed to a high-temperature environment for a long period of time. Another object of the present invention is to provide an organic EL display device. [Means for solving the problem]

[0007] As a result of extensive investigation into the problems of the conventional techniques, the present inventors have found that the above-mentioned problems can be solved by the following configuration.

[0008] (1) a polarizer formed using a composition containing a first liquid crystal compound and a dichroic material; an optically anisotropic layer formed using a composition containing a second liquid crystal compound and disposed adjacent to the polarizer; A polarizing plate, in which the content of a dichroic material in a polarizer is 40 mass % or less with respect to the total mass of the polarizer. (2) The polarizing plate according to (1), wherein the content of the dichroic material in the polarizer is 30 mass % or less based on the total mass of the polarizer. (3) The polarizing plate according to (1) or (2), wherein the angle between the absorption axis of the polarizer and the in-plane slow axis of the surface of the optically anisotropic layer facing the polarizer is within 1°. (4) The polarizing plate according to any one of (1) to (3), wherein the optically anisotropic layer is a layer in which a second liquid crystal compound is fixed and twisted and aligned with a helical axis in the thickness direction. (5) The optically anisotropic layer has a plurality of layers each including a second liquid crystal compound fixed in a helical orientation with the thickness direction as a helical axis, The polarizing plate according to any one of (1) to (4), wherein the second liquid crystal compound in each of the plurality of layers has a different twist angle. (6) The optically anisotropic layer has a plurality of layers each including a second liquid crystal compound fixed in a helical orientation with the thickness direction as a helical axis, The polarizing plate according to any one of (1) to (5), wherein the plurality of layers each have a different ratio of the twist angle of the second liquid crystal compound to the layer thickness. (7) The optically anisotropic layer has a first optically anisotropic layer and a second optically anisotropic layer, a first optically anisotropic layer disposed on the polarizer side; the first optically anisotropic layer and the second optically anisotropic layer are layers in which a second liquid crystal compound is fixed and twisted in a helical axis along the thickness direction; the twist direction of the second liquid crystal compound in the first optically anisotropic layer is the same as the twist direction of the second liquid crystal compound in the second optically anisotropic layer; the twist angle of the second liquid crystal compound in the first optically anisotropic layer is 26.5±10.0°; the twist angle of the second liquid crystal compound in the second optically anisotropic layer is 78.6±10.0°; an in-plane slow axis of the first optically anisotropic layer on the second optically anisotropic layer side is parallel to an in-plane slow axis of the second optically anisotropic layer on the first optically anisotropic layer side; The polarizing plate according to any one of (1) to (6), wherein the product Δn1·d1 of the refractive index anisotropy Δn1 of the first optically anisotropic layer measured at a wavelength of 550 nm and the thickness d1 of the first optically anisotropic layer, and the product Δn2·d2 of the refractive index anisotropy Δn2 of the second optically anisotropic layer measured at a wavelength of 550 nm and the thickness d2 of the second optically anisotropic layer, satisfy the following formulas (1) and (2), respectively. Formula (1) 252nm≦Δn1·d1≦312nm Formula (2) 110nm≦Δn2·d2≦170nm (8) The polarizing plate according to any one of (1) to (7), in which, when a component analysis in the depth direction of the polarizer is performed by time-of-flight secondary ion mass spectrometry, the relationship between the maximum intensity Imax of the secondary ion intensity originating from the dichroic substance and the intensity Isur1 of the secondary ion intensity originating from the dichroic substance on the surface of the polarizer opposite to the optically anisotropic layer side satisfies formula (3). Equation (3) 2.0≦Imax / Isur1 (9) The polarizing plate according to any one of (1) to (8), wherein the absolute value of the difference between the logP of the second liquid crystal compound and the logP of the dichroic material is 3.0 or more. (10) An organic electroluminescence display device having the polarizing plate according to any one of (1) to (9). Effect of the Invention

[0009] According to the present invention, a polarizing plate can be provided that exhibits excellent black density in the front direction even after the organic EL display device obtained by attaching the polarizing plate to an organic EL display panel is exposed to a high-temperature environment for a long period of time. Moreover, the present invention can provide an organic EL display device. [Brief description of the drawings]

[0010] [Figure 1] 1 is a schematic cross-sectional view of one embodiment of a polarizing plate of the present invention. [Diagram 2] FIG. 2 is a schematic diagram for explaining a profile in the depth direction of secondary ion intensity of each component detected by analyzing the components in the depth direction of a polarizing plate by time-of-flight secondary ion mass spectrometry (TOF-SIMS). [Diagram 3] FIG. 1 is a schematic cross-sectional view of a preferred embodiment of a polarizing plate of the present invention. [Figure 4] FIG. 2 is a diagram showing the relationship between the absorption axis of a polarizer 12 and the in-plane slow axes of a first optically anisotropic layer 16 and a second optically anisotropic layer 18 in a preferred embodiment of the polarizing plate of the present invention. [Diagram 5] 5 is a schematic diagram showing the relationship between the absorption axis of a polarizer 12 and the angle between the in-plane slow axes of a first optically anisotropic layer 16 and a second optically anisotropic layer 18 when observed from the direction of the arrow in FIG. [Figure 6] FIG. 2 is a cross-sectional view of a composition layer for explaining step 1. [Figure 7] FIG. 11 is a cross-sectional view of a composition layer for explaining step 2. [Figure 8]FIG. 2 is a schematic diagram of a graph plotting the relationship between the helical twisting power (HTP) (μm−1)×concentration (mass%) and the light irradiation dose (mJ / cm2) for each of chiral agent A and chiral agent B. [Figure 9] FIG. 1 is a schematic diagram of a graph plotting the relationship between the weighted average helical twisting power (μm−1) and the light irradiation dose (mJ / cm2) in a system in which chiral agent A and chiral agent B are used in combination. [Figure 10] FIG. 4 is a cross-sectional view of a composition layer for explaining step 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in detail below. In this specification, a numerical range expressed using "to" means a range including the numerical values ​​before and after "to" as the lower and upper limits. First, the terms used in this specification will be described.

[0012] The in-plane slow axis is defined at 550 nm unless otherwise specified.

[0013] In the present invention, Re(λ) and Rth(λ) respectively represent the in-plane retardation and the retardation in the thickness direction at a wavelength λ, which is set to 550 nm unless otherwise specified. In the present invention, Re(λ) and Rth(λ) are values ​​measured at a wavelength λ using an AxoScan (manufactured by Axometrics). By inputting the average refractive index ((nx+ny+nz) / 3) and the film thickness (d(μm)) into AxoScan, Slow axis direction (°) Re(λ)=R0(λ) Rth(λ)=((nx+ny) / 2-nz)×d is calculated. Note that R0(λ) is displayed as a numerical value calculated by AxoScan, but it means Re(λ).

[0014] In this specification, the refractive indices nx, ny, and nz are measured using an Abbe refractometer (NAR-4T, manufactured by Atago Co., Ltd.) and a sodium lamp (λ=589 nm) as a light source. In addition, when measuring wavelength dependency, it can be measured using a multi-wavelength Abbe refractometer DR-M2 (manufactured by Atago Co., Ltd.) in combination with an interference filter. In addition, values ​​from the Polymer Handbook (JOHN WILEY & SONS, INC.) and catalogs of various optical films can be used. The average refractive index values ​​of major optical films are shown below as examples: cellulose acylate (1.48), cycloolefin polymer (1.52), polycarbonate (1.59), polymethyl methacrylate (1.49), and polystyrene (1.59).

[0015] In this specification, the term "light" refers to actinic rays or radiation, such as the bright line spectrum of a mercury lamp, far ultraviolet rays represented by an excimer laser, extreme ultraviolet rays (EUV light: extreme ultraviolet), X-rays, ultraviolet rays, and electron beams (EB), etc. Among these, ultraviolet rays are preferred.

[0016] In this specification, "visible light" refers to light having a wavelength of 380 to 780 nm. In addition, in this specification, unless otherwise specified, the measurement wavelength is 550 nm. In this specification, the angular relationship (e.g., "perpendicular", "parallel", etc.) is assumed to include the range of error permitted in the technical field to which the present invention pertains. Specifically, this means that the angle is within a range of less than ±10° from the exact angle, and the error from the exact angle is preferably within a range of ±5° or less, and more preferably within a range of ±3° or less.

[0017] The bonding direction of a divalent group (e.g., -C(O)O-) described in this specification is not particularly limited. For example, when L1 in formula (1) described later is -C(O)O-, when the position bonded to the P1 side is *1 and the position bonded to the SP1 side is *2, L1 may be *1-C(O)-O-*2 or *1-OC(O)-*2.

[0018] The polarizing plate of the present invention is characterized in that the polarizer and the optically anisotropic layer are in direct contact with each other, and the concentration of the dichroic material in the polarizer is equal to or less than a predetermined value. The present inventors have investigated the reason why the polarizing plate described in Patent Document 1 does not achieve the desired effect, and firstly, when a pressure-sensitive adhesive layer is interposed between the polarizer and the optically anisotropic layer, light reflection is likely to occur at the interface between the polarizer and the pressure-sensitive adhesive layer and at the interface between the pressure-sensitive adhesive layer and the optically anisotropic layer, which is one of the causes of deterioration in tightness of black. In particular, since the polarizer contains a dichroic material with a relatively high refractive index, the refractive index of the polarizer itself becomes high, and the refractive index difference between adjacent pressure-sensitive adhesive layers becomes large, which makes light reflection more likely to occur. In contrast, in the present invention, the polarizer and the optically anisotropic layer are brought into direct contact with each other, thereby suppressing the reflection of light from the adhesive layer, and the concentration of the dichroic material in the polarizer is set to a predetermined value or less, thereby adjusting the refractive index of the polarizer to a refractive index similar to that of the optically anisotropic layer, thereby suppressing the reflection of light at the interface between the polarizer and the optically anisotropic layer.

[0019] The polarizing plate of the present invention will now be described with reference to the drawings. Fig. 1 is a schematic cross-sectional view of one embodiment of the polarizing plate of the present invention. Polarizing plate 10A has a polarizer 12 and an optically anisotropic layer 14. As shown in Fig. 1, the polarizer 12 and the optically anisotropic layer 14 are disposed adjacent to each other. In other words, the polarizer 12 and the optically anisotropic layer 14 are disposed so as to be in direct contact with each other.

[0020] Here, adjacent to each other means that the polarizer and the optically anisotropic layer are disposed without any other layer such as a pressure-sensitive adhesive layer therebetween. The manner in which the polarizer 12 and the optically anisotropic layer 14 are disposed adjacent to each other can also be determined by using time-of-flight secondary ion mass spectrometry as described below. More specifically, first, an ion beam is irradiated from one surface of the polarizing plate to the other surface while analyzing the components in the depth direction of the polarizing plate using time-of-flight secondary ion mass spectrometry, and a depth profile of the secondary ion intensity originating from the components contained in the polarizer and the secondary ion intensity originating from the components contained in the optically anisotropic layer is obtained. Fig. 2 shows a profile obtained by analyzing the components in the depth direction of each layer by TOF-SIMS while ion sputtering from the polarizer side surface of the polarizing plate toward the optically anisotropic layer side. Note that in this specification, the depth direction means the direction toward the optically anisotropic layer side with the polarizer side surface of the polarizing plate as the reference. In the depth profile shown in FIG. 2, the horizontal axis (the axis extending left-right on the paper in FIG. 2) represents the depth based on the surface on the polarizer side of the polarizing plate, and the vertical axis (the axis extending up-down on the paper in FIG. 2) represents the secondary ion intensity of each component. The TOF-SIMS method is specifically described in "Surface Analysis Techniques Selection: Secondary Ion Mass Analysis Methods" edited by the Japanese Surface Science Society, published by Maruzen Co., Ltd. (1999).

[0021] In addition, when analyzing the components in the depth direction of the polarizing plate using TOF-SIMS while irradiating it with an ion beam, a series of operations is repeated, in which component analysis is performed in a surface depth region of 1 to 2 nm, and then the sample is excavated further in the depth direction by 1 nm to several hundred nm to perform component analysis in the next surface depth region of 1 to 2 nm.

[0022] The depth profile shown in Figure 2 shows the results of the secondary ion intensity originating from the components contained in the polarizer (line C1 in the figure) and the results of the secondary ion intensity originating from the components contained in the optically anisotropic layer (line C2 in the figure). In this specification, the "secondary ion intensity originating from the components contained in the polarizer" determined from the depth profile detected by analyzing the components in the depth direction of the polarizing plate using TOF-SIMS refers to the intensity of fragment ions originating from the components contained in the polarizer, and the "secondary ion intensity originating from the components contained in the optically anisotropic layer" refers to the intensity of fragment ions originating from the components contained in the optically anisotropic layer.

[0023] As shown in Figure 2, when the components in the depth direction of a polarizing plate are analyzed by TOF-SIMS while irradiating an ion beam from the polarizer side surface of the polarizing plate toward the optically anisotropic layer side, the secondary ion intensity originating from the components contained in the polarizer is observed to be high at first, and as the ion beam is irradiated further in the depth direction, the secondary ion intensity gradually decreases. On the other hand, from a certain depth position, the secondary ion intensity originating from the components contained in the optically anisotropic layer gradually increases, and from a certain depth position onwards, the secondary ion intensity originating from the components contained in the polarizer is not observed, and the secondary ion intensity originating from the components contained in the optically anisotropic layer is observed to be high. When the polarizer and the optically anisotropic layer are adjacent to each other, a profile (line) showing the secondary ion intensity originating from the component contained in the polarizer and a profile (line) showing the secondary ion intensity originating from the component contained in the optically anisotropic layer intersect at a predetermined depth position P as shown in Fig. 2. In other words, near the interface between the polarizer and the optically anisotropic layer, there exists a depth position where the secondary ion intensity originating from the component contained in the polarizer and the secondary ion intensity originating from the component contained in the optically anisotropic layer show the same intensity.

[0024] The TOF-SIMS method may be performed using known methods. For example, the measurement apparatus and measurement conditions are as follows: Equipment: TOF-SIMS 5 (ION-TOF) Depth profile analysis: Combined with Ar ion sputtering Measurement range: Raster scan of 128 points in one direction and in the orthogonal direction ·Polarity: posi, negative

[0025] When obtaining the secondary ion intensity profile, for example, a dichroic material or a first liquid crystal compound is selected as a component contained in the polarizer. In addition, a second liquid crystal compound is selected as the component contained in the optically anisotropic layer.

[0026] Each member included in the polarizing plate will be described in detail below.

[0027] <Polarizer> The polarizer is formed using a composition (hereinafter also referred to as a polarizer-forming composition) containing a first liquid crystal compound and a dichroic substance. In the polarizer, the dichroic substance is also aligned in a predetermined direction along the alignment of the first liquid crystal compound. In particular, it is preferable that the dichroic substance is aligned horizontally. The materials used to form the polarizer will first be described in detail below.

[0028] (1st liquid crystal compound) As the first liquid crystal compound, either a polymer liquid crystal compound or a low molecular weight liquid crystal compound can be used, and it is preferable to use a polymer liquid crystal compound since it will result in a higher degree of orientation of the dichroic material. Here, the term "polymeric liquid crystal compound" refers to a liquid crystal compound having a repeating unit in the chemical structure. Moreover, the term "low molecular weight liquid crystal compound" refers to a liquid crystal compound that does not have a repeating unit in its chemical structure. Examples of the polymer liquid crystal compound include the thermotropic liquid crystal polymer described in JP 2011-237513 A and the polymer liquid crystal compound described in paragraphs

[0012] to

[0042] of WO 2018 / 199096 A. Examples of the low molecular weight liquid crystal compound include the liquid crystal compounds described in paragraphs

[0072] to

[0088] of JP2013-228706A. Among them, liquid crystal compounds exhibiting smectic properties are preferable. As the first liquid crystal compound, a polymer liquid crystal compound and a low molecular liquid crystal compound may be used in combination.

[0029] As the first liquid crystal compound, a polymer liquid crystal compound containing a repeating unit represented by the following formula (1) (hereinafter also abbreviated as "repeating unit (1)") is preferable, since it provides a higher degree of orientation of the dichroic material.

[0030] [ka]

[0031] In the above formula (1), P1 represents the main chain of the repeating unit, L1 represents a single bond or a divalent linking group, SP1 represents a spacer group, M1 represents a mesogenic group, and T1 represents a terminal group.

[0032] Examples of the main chain of the repeating unit represented by P1 include groups represented by the following formulae (P1-A) to (P1-D). Among these, the group represented by the following formula (P1-A) is preferred in terms of the variety of monomers that serve as raw materials and ease of handling.

[0033] [ka]

[0034] In the above formulas (P1-A) to (P1-D), "*" represents the bonding position with L1 in the above formula (1). In the above formulas (P1-A) to (P1-D), R 1 , R 2 , R 3 and R 4 each independently represents a hydrogen atom, a halogen atom, a cyano group, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms. The alkyl group may be a linear or branched alkyl group, or an alkyl group having a cyclic structure (cycloalkyl group). The number of carbon atoms in the alkyl group is preferably 1 to 5. The group represented by the above formula (P1-A) is preferably one unit of a partial structure of a poly(meth)acrylic acid ester obtained by polymerization of a (meth)acrylic acid ester. The group represented by the above formula (P1-B) is preferably an ethylene glycol unit formed by ring-opening polymerization of the epoxy group of a compound having an epoxy group. The group represented by the above formula (P1-C) is preferably a propylene glycol unit formed by ring-opening polymerization of the oxetane group of a compound having an oxetane group. The group represented by the formula (P1-D) is preferably a siloxane unit of a polysiloxane obtained by condensation polymerization of a compound having at least one of an alkoxysilyl group and a silanol group. Here, the compound having at least one of an alkoxysilyl group and a silanol group is preferably a compound represented by the formula SiR 4 (OR 5 )2-, wherein R 4 is R in (P1-D) 4 Synonymous with R 5 each independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms.

[0035] In the above formula (1), L1 is a single bond or a divalent linking group. The divalent linking group represented by L1 is -C(O)O-, -O-, -S-, or -C(O)NR 6 -, -SO2-, and -NR 6 R 7 In the formula, R 6 and R 7 each independently represents a hydrogen atom or an optionally substituted alkyl group having 1 to 6 carbon atoms. When P1 is a group represented by formula (P1-A), L1 is preferably a group represented by -C(O)O-, since this leads to a higher degree of orientation of the dichroic material. When P1 is a group represented by any of the formulae (P1-B) to (P1-D), L1 is preferably a single bond since the degree of orientation of the dichroic material is higher.

[0036] In the above formula (1), the spacer group represented by SP1 preferably contains at least one structure selected from the group consisting of an oxyethylene structure, an oxypropylene structure, a polysiloxane structure, and an alkylene fluoride structure, from the viewpoints of ease of expressing liquid crystallinity and availability of raw materials. Here, the oxyethylene structure represented by SP1 is *-(CH2-CH2O) n1A group represented by -* is preferred. In the formula, n1 represents an integer of 1 to 20, and * represents the bonding position with L1 or M1 in the above formula (1). n1 is preferably an integer of 2 to 10, more preferably an integer of 2 to 4, and most preferably 3, in order to increase the degree of orientation of the dichroic material. In addition, the oxypropylene structure represented by SP1 is *-(CH(CH3)-CH2O) because it increases the degree of orientation of the dichroic material. n2 A group represented by -* is preferred, in which n2 represents an integer of 1 to 3, and * represents the bonding position to L1 or M1. In addition, the polysiloxane structure represented by SP1 is *-(Si(CH3)2-O) because it increases the degree of orientation of the dichroic material. n3 A group represented by -* is preferred, in which n3 represents an integer of 6 to 10, and * represents the bonding position to L1 or M1. In addition, the fluorinated alkylene structure represented by SP1 is preferred because it increases the degree of orientation of the dichroic material. n4 A group represented by -* is preferred, in which n4 represents an integer of 6 to 10, and * represents the bonding position to L1 or M1.

[0037] In the above formula (1), the mesogenic group represented by M1 is a group that represents the main skeleton of the liquid crystal molecule that contributes to the formation of liquid crystal. The liquid crystal molecule exhibits liquid crystallinity, which is an intermediate state (mesophase) between the crystalline state and the isotropic liquid state. There are no particular limitations on the mesogenic group, and reference can be made to, for example, the description in "Flussige Kristalle in Tabellen II" (VEB Deutsche Verlag fur Grundstoff Industrie, Leipzig, 19th issue, published in 2000), particularly Chapter 3. The mesogenic group is preferably, for example, a group having at least one cyclic structure selected from the group consisting of an aromatic hydrocarbon group, a heterocyclic group, and an alicyclic group. The mesogenic group preferably has an aromatic hydrocarbon group, more preferably has 2 to 4 aromatic hydrocarbon groups, and even more preferably has 3 aromatic hydrocarbon groups, in order to increase the degree of orientation of the dichroic substance.

[0038] As the mesogenic group, from the viewpoints of expression of liquid crystallinity, adjustment of the liquid crystal phase transition temperature, availability of raw materials and suitability for synthesis, as well as a higher degree of orientation of the dichroic substance, a group represented by the following formula (M1-A) or formula (M1-B) is preferred, and a group represented by formula (M1-B) is more preferred.

[0039] [ka]

[0040] In formula (M1-A), A1 is a divalent group selected from the group consisting of aromatic hydrocarbon groups, heterocyclic groups, and alicyclic groups. These groups may be substituted with an alkyl group, a fluorinated alkyl group, an alkoxy group, or a substituent. The divalent group represented by A1 is preferably a 4- to 6-membered ring. In addition, the divalent group represented by A1 may be a monocyclic ring or a condensed ring. * indicates the binding position to SP1 or T1.

[0041] Examples of the divalent aromatic hydrocarbon group represented by A1 include a phenylene group, a naphthylene group, a fluorene-diyl group, an anthracene-diyl group, and a tetracene-diyl group. From the viewpoints of the diversity of mesogenic skeleton designs and the availability of raw materials, a phenylene group or a naphthylene group is preferred, and a phenylene group is more preferred.

[0042] The divalent heterocyclic group represented by A1 may be either aromatic or non-aromatic, but is preferably a divalent aromatic heterocyclic group since it results in a higher degree of orientation of the dichroic material. The atoms other than carbon constituting the divalent aromatic heterocyclic group include a nitrogen atom, a sulfur atom, and an oxygen atom. When the aromatic heterocyclic group has a plurality of atoms other than carbon constituting the ring, these atoms may be the same or different. Examples of divalent aromatic heterocyclic groups include a pyridylene group (pyridine-diyl group), a pyridazine-diyl group, an imidazole-diyl group, a thienylene group (thiophene-diyl group), a quinolylene group (quinoline-diyl group), an isoquinolylene group (isoquinoline-diyl group), an oxazole-diyl group, a thiazole-diyl group, an oxadiazole-diyl group, a benzothiazole-diyl group, a benzothiadiazole-diyl group, a phthalimido-diyl group, a thienothiazole-diyl group, a thiazolothiazole-diyl group, a thienothiophene-diyl group, and a thienoxazole-diyl group.

[0043] Examples of the divalent alicyclic group represented by A1 include a cyclopentylene group and a cyclohexylene group.

[0044] In formula (M1-A), a1 represents an integer of 1 to 10. When a1 is 2 or more, multiple A1 may be the same or different.

[0045] In formula (M1-B), A2 and A3 are each independently a divalent group selected from the group consisting of an aromatic hydrocarbon group, a heterocyclic group, and an alicyclic group. Specific examples and preferred embodiments of A2 and A3 are the same as those of A1 in formula (M1-A), and therefore the description thereof is omitted. In formula (M1-B), a2 represents an integer of 1 to 10, and when a2 is 2 or more, multiple A2 may be the same or different, multiple A3 may be the same or different, and multiple LA1 may be the same or different. a2 is preferably an integer of 2 or more, and more preferably 2, in order to increase the degree of orientation of the dichroic material. In formula (M1-B), when a2 is 1, LA1 is a divalent linking group. When a2 is 2 or more, each of the multiple LA1 is independently a single bond or a divalent linking group, and at least one of the multiple LA1 is a divalent linking group. When a2 is 2, it is preferable that one of the two LA1 is a divalent linking group and the other is a single bond, since this increases the degree of orientation of the dichroic material.

[0046] In formula (M1-B), examples of the divalent linking group represented by LA1 include -O-, -(CH2) g -, -(CF2) g -, -Si(CH3)2-, -(Si(CH3)2O) g -, -(OSi(CH3)2) g -(g represents an integer from 1 to 10.), -N(Z)-, -C(Z)=C(Z')-, -C(Z)=N-, -N=C(Z)-, -C(Z)2- C(Z')2-, -C(O)-, -OC(O)-, -C(O)O-, -OC(O)O-, -N(Z)C(O)-, -C(O)N(Z)-, - C(Z)=C(Z')-C(O)O-, -OC(O)-C(Z)=C(Z')-, -C(Z)=N-, -N=C(Z)-, -C(Z)=C (Z')-C(O)N(Z”)-, -N(Z”)-C(O)-C(Z)=C(Z')-, -C(Z)=C(Z')-C(O)-S-, -SC Examples of such groups include (O)-C(Z)=C(Z')-, -C(Z)=NN=C(Z')- (Z, Z', and Z" each independently represent a hydrogen atom, a C1 to C4 alkyl group, a cycloalkyl group, an aryl group, a cyano group, or a halogen atom), -C≡C-, -N=N-, -S-, -S(O)-, -S(O)(O)-, -(O)S(O)O-, -O(O)S(O)O-, -SC(O)-, and -C(O)S-. Of these, -C(O)O- is preferred because it results in a higher degree of orientation of the dichroic substance. LA1 may be a group consisting of a combination of two or more of these groups.

[0047] In the above formula (1), examples of the terminal group represented by T1 include a hydrogen atom, a halogen atom, a cyano group, a nitro group, a hydroxy group, an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, an alkylthio group having 1 to 10 carbon atoms, an alkoxycarbonyloxy group having 1 to 10 carbon atoms, an alkoxycarbonyl group having 1 to 10 carbon atoms (ROC(O)-: R is an alkyl group), an acyloxy group having 1 to 10 carbon atoms, an acylamino group having 1 to 10 carbon atoms, an alkoxycarbonylamino group having 1 to 10 carbon atoms, a sulfonylamino group having 1 to 10 carbon atoms, a sulfamoyl group having 1 to 10 carbon atoms, a carbamoyl group having 1 to 10 carbon atoms, a sulfinyl group having 1 to 10 carbon atoms, a ureido group having 1 to 10 carbon atoms, and a (meth)acryloyloxy group-containing group. Examples of the (meth)acryloyloxy group-containing group include a group represented by -LA (L represents a single bond or a linking group. Specific examples of the linking group are the same as those of L1 and SP1 described above. A represents a (meth)acryloyloxy group).

[0048] T1 is preferably an alkoxy group having 1 to 10 carbon atoms, more preferably an alkoxy group having 1 to 5 carbon atoms, and further preferably a methoxy group, in that the degree of orientation of the dichroic material is higher. These end groups may be further substituted with these groups or with polymerizable groups as described in JP 2010-244038 A.

[0049] T1 is preferably a polymerizable group, since this improves the adhesion between the polarizer and the optically anisotropic layer and improves the cohesive strength of the film. The polymerizable group is preferably a radically polymerizable group or a cationic polymerizable group. As the radical polymerizable group, a generally known radical polymerizable group can be used, and an acryloyl group or a methacryloyl group is preferred. In this case, it is known that the polymerization rate of an acryloyl group is generally fast, and an acryloyl group is preferred from the viewpoint of improving productivity, but a methacryloyl group can also be used as the polymerizable group. As the cationic polymerizable group, a generally known cationic polymerizable group can be used, for example, an alicyclic ether group, a cyclic acetal group, a cyclic lactone group, a cyclic thioether group, a spiro orthoester group, and a vinyloxy group can be mentioned. Among them, an alicyclic ether group or a vinyloxy group is preferable, and an epoxy group, an oxetanyl group, or a vinyloxy group is more preferable.

[0050] The weight average molecular weight (Mw) of the polymer liquid crystal compound containing the repeating unit represented by the above formula (1) is preferably from 1000 to 500000, more preferably from 2000 to 300000. When the Mw of the polymer liquid crystal compound is within the above range, the polymer liquid crystal compound is easy to handle. In particular, from the viewpoint of suppressing cracks during coating, the weight average molecular weight (Mw) of the polymer liquid crystal compound is preferably 10,000 or more, and more preferably 10,000 to 300,000. From the viewpoint of the temperature latitude of the orientation degree, the weight average molecular weight (Mw) of the polymer liquid crystal compound is preferably less than 10,000, and more preferably 2,000 or more and less than 10,000. Here, the weight average molecular weight and number average molecular weight in the present invention are values ​​measured by gel permeation chromatography (GPC). Solvent (eluent): N-methylpyrrolidone ·Device name: TOSOH HLC-8220GPC Column: Three TOSOH TSKgel SuperAWM-H (6 mm x 15 cm) columns connected together Column temperature: 25℃ Sample concentration: 0.1% by mass ·Flow rate: 0.35mL / min Calibration curve: TOSOH TSK standard polystyrene Calibration curve using 7 samples with Mw = 2,800,000 to 1,050 (Mw / Mn = 1.03 to 1.06)

[0051] The content of the first liquid crystal compound is preferably 50% by mass or more, more preferably 70% by mass or more, based on the total solid content of the composition for forming a polarizer. Although there is no particular upper limit, it is often 95% by mass or less. Here, "total solid content of the polarizer-forming composition" refers to the components in the polarizer-forming composition excluding the solvent, and specific examples of the solid content include the first liquid crystal compound, the dichroic substance described below, the polymerization initiator, and the surfactant.

[0052] (dichroic substance) The dichroic substance is not particularly limited, and examples thereof include visible light absorbing substances (dichroic dyes), luminescent substances (fluorescent substances, phosphorescent substances), ultraviolet absorbing substances, infrared absorbing substances, nonlinear optical substances, carbon nanotubes, and inorganic substances (e.g., quantum rods), and any conventionally known dichroic substance (dichroic dye) can be used. For example, paragraphs

[0067] to

[0071] of JP 2013-228706 A, paragraphs

[0008] to

[0026] of JP 2013-227532 A, paragraphs

[0008] to

[0015] of JP 2013-209367 A, paragraphs

[0045] to

[0058] of JP 2013-014883 A, paragraphs

[0012] to

[0029] of JP 2013-109090 A, and paragraphs

[0009] to [ 0017], paragraphs

[0051] to

[0065] of JP 2013-037353 A, paragraphs

[0049] to

[0073] of JP 2012-063387 A, paragraphs

[0016] to

[0018] of JP 11-305036 A, paragraphs

[0009] to

[0011] of JP 2001-133630 A, paragraphs

[0030] to

[0169] of JP 2011-215337 A, and paragraphs

[0021] to [

[0075] , paragraphs

[0011] to

[0025] of JP 2010-215846 A, paragraphs

[0017] to

[0069] of JP 2011-048311 A, paragraphs

[0013] to

[0133] of JP 2011-213610 A, paragraphs

[0074] to

[0246] of JP 2011-237513 A, paragraphs

[0005] to

[0051] of JP 2016-006502 A, and [000 Examples of the compound described in the above include those described in paragraphs

[0014] to

[0033] of WO2017 / 154835, paragraphs

[0014] to

[0033] of WO2017 / 154695, paragraphs

[0013] to

[0037] of WO2017 / 195833, and paragraphs

[0014] to

[0034] of WO2018 / 164252.

[0053] In the present invention, two or more dichroic substances may be used in combination. For example, from the viewpoint of making the resulting polarizer closer to black, it is preferable to use in combination at least one dichroic substance having a maximum absorption wavelength in the wavelength range of 370 nm or more and less than 500 nm and at least one dichroic substance having a maximum absorption wavelength in the wavelength range of 500 nm or more and less than 700 nm.

[0054] The dichroic substance may have a crosslinkable group. Examples of the crosslinkable group include a (meth)acryloyl group, an epoxy group, an oxetanyl group, and a styryl group, and among these, a (meth)acryloyl group is preferable.

[0055] The content of the dichroic substance is preferably from 2 to 80 parts by mass, and more preferably from 5 to 30 parts by mass, based on 100 parts by mass of the liquid crystal compound. The content of the dichroic material is preferably from 1 to 40 mass %, and more preferably from 2 to 30 mass %, of the solid content in the polarizer-forming composition.

[0056] (Other Ingredients) The composition for forming a polarizer may contain other components in addition to the first liquid crystal compound and the dichroic material described above.

[0057] The composition for forming a polarizer preferably contains a polymerization initiator. The polymerization initiator is not particularly limited, but a photosensitive compound, that is, a photopolymerization initiator, is preferred. As the photopolymerization initiator, various compounds can be used without any particular limitation. Examples of the photopolymerization initiator include α-carbonyl compounds (U.S. Pat. Nos. 2,367,661 and 2,367,670), acyloin ethers (U.S. Pat. No. 2,448,828), α-hydrocarbon-substituted aromatic acyloin compounds (U.S. Pat. No. 2,722,512), polynuclear quinone compounds (U.S. Pat. Nos. 3,046,127 and 2,951,758), combinations of triaryl imidazole dimers and p-aminophenyl ketones (U.S. Pat. No. 3,549,367), and the like. documents), acridine and phenazine compounds (JP 60-105667 A and U.S. Pat. No. 4,239,850 A), oxadiazole compounds (U.S. Pat. No. 4,212,970 A), o-acyloxime compounds (JP 2016-027384 A

[0065] ), and acylphosphine oxide compounds (JP 63-040799 A, JP 5-029234 A, JP 10-095788 A, and JP 10-029997 A).

[0058] When the polarizer-forming composition contains a polymerization initiator, the content of the polymerization initiator is preferably 0.01 to 30 parts by mass, and more preferably 0.1 to 15 parts by mass, per 100 parts by mass of the dichroic substance and the liquid crystal compound in total.

[0059] The composition for forming a polarizer preferably contains a surfactant. By including a surfactant, it is expected that the smoothness of the coating surface will be improved, the degree of orientation will be further improved, and repelling and unevenness will be suppressed, thereby improving the uniformity within the surface. The surfactant is preferably one that aligns the dichroic substance and the liquid crystal compound horizontally on the coating surface side, and examples thereof include the compounds described in paragraphs

[0155] to

[0170] of WO 2016 / 009648 and the compounds (horizontal alignment agents) described in paragraphs

[0253] to

[0293] of JP 2011-237513 A.

[0060] When the polarizer-forming composition contains a surfactant, the content of the surfactant is preferably 0.001 to 5 parts by mass, and more preferably 0.01 to 3 parts by mass, per 100 parts by mass of the dichroic substance and the liquid crystal compound in total.

[0061] From the viewpoint of workability, the composition for forming a polarizer preferably contains a solvent. Examples of the solvent include organic solvents such as ketones, ethers, aliphatic hydrocarbons, alicyclic hydrocarbons, aromatic hydrocarbons, halogenated carbons, esters, alcohols, cellosolves, cellosolve acetates, sulfoxides, amides, and heterocyclic compounds, as well as water. These solvents may be used alone or in combination of two or more.

[0062] When the polarizer-forming composition contains a solvent, the content of the solvent is preferably from 80 to 99 mass %, and more preferably from 83 to 97 mass %, based on the total mass of the polarizer-forming composition.

[0063] (Method of manufacturing polarizer) The method for producing a polarizer is not particularly limited as long as a polarizer-forming composition is used, but a method in which the polarizer-forming composition is applied onto a specified support to form a coating film and the liquid crystalline component in the coating film is aligned is preferred. The liquid crystal component is a component including not only the first liquid crystal compound described above, but also a dichroic substance having liquid crystal properties when the dichroic substance described above has liquid crystal properties.

[0064] The support on which the polarizer-forming composition is applied is not particularly limited, and will be described in detail later. The support may have an alignment layer on its surface. Methods for forming an alignment film include, for example, rubbing an organic compound (preferably a polymer) onto the film surface, oblique deposition of an inorganic compound, formation of a layer having microgrooves, and accumulation of an organic compound (e.g., ω-tricosanoic acid, dioctadecylmethylammonium chloride, methyl stearate, etc.) by the Langmuir-Blodgett method (LB film). The alignment layer is preferably an alignment film formed by a rubbing treatment or a photo-alignment film formed by light irradiation. The photo-alignment compound contained in the photo-alignment film may be a known material. As the photo-alignment compound, it is preferable to use a photosensitive compound having a photoreactive group that undergoes at least one of dimerization and isomerization by the action of light. Furthermore, a composition for forming a polarizer may be applied onto an optically anisotropic layer, which will be described later. In this case, the optically anisotropic layer functions as an alignment film.

[0065] The method for applying the composition for forming a polarizer is not particularly limited, and examples of the method include curtain coating, dip coating, spin coating, print coating, spray coating, slot coating, roll coating, slide coating, blade coating, gravure coating, and wire bar coating.

[0066] The method for orienting the liquid crystal component in the coating film is not particularly limited, and heat treatment is preferred. From the viewpoint of manufacturability, the heat treatment temperature is preferably from 10 to 250° C., more preferably from 25 to 190° C. The heating time is preferably from 1 to 300 seconds, more preferably from 1 to 60 seconds. After the heating treatment, a cooling treatment may be carried out as necessary. The cooling treatment is a treatment for cooling the coated film after heating to about room temperature (20 to 25°C). This allows the alignment of the liquid crystal component contained in the coated film to be fixed. The cooling means is not particularly limited, and can be carried out by a known method.

[0067] After the liquid crystal component is aligned, a curing treatment may be carried out, if necessary. When the polarizer contains a crosslinkable group (polymerizable group), the curing treatment is carried out by heating and / or light irradiation (exposure).

[0068] (Characteristics of polarizers) The content of the dichroic material in the polarizer is 40% by mass or less with respect to the total mass of the polarizer. In particular, the content of the dichroic material is preferably 30% by mass or less with respect to the total mass of the polarizer, in order to provide better black density in the front direction even after a display device including the polarizer of the present invention is exposed to a high-temperature environment for a long period of time (hereinafter, also referred to as "the effect of the present invention is better"). The lower limit of the content of the dichroic material is not particularly limited, but is preferably 3% by mass or more, more preferably 5% by mass or more with respect to the total mass of the polarizer.

[0069] When a component analysis is performed in the depth direction of the polarizer by time-of-flight secondary ion mass spectrometry, the relationship between the maximum intensity Imax of the secondary ion intensity originating from the dichroic material and the intensity Isur1 of the secondary ion intensity originating from the dichroic material on the surface of the polarizer opposite the optically anisotropic layer preferably satisfies formula (3), more preferably formula (3-1), and even more preferably formula (3-2). By satisfying the relationship of formula (3), the display performance and durability are good even without providing a refractive index adjustment layer or a barrier layer (oxygen barrier layer), and thus the organic EL display device can be made thinner. Equation (3) 2.0≦Imax / Isur1 Formula (3-1) 5.0≦Imax / Isur1 Formula (3-2) 10.0 <Imax / Isur1≦100

[0070] The average secondary ion intensity of fragments derived from dichroic substances (average intensity from the baseline) in a 1% region from the surface of the polarizer opposite the optically anisotropic layer is defined as the intensity Isur1 on the viewing side surface. In addition, the maximum value of the secondary ion intensity (intensity from the baseline) of the fragments derived from the dichroic material in a region of 98% of the total thickness excluding 1% of the total thickness from each surface is defined as the maximum intensity Imax in the thickness direction. The measurement method of time-of-flight secondary ion mass spectrometry includes the above-mentioned methods. In addition, when the polarizer contains two or more types of dichroic substances, the secondary ion intensity of the fragment derived from the dichroic substance having a maximum absorption wavelength in the wavelength range of 500 to 650 nm (hereinafter also referred to as the "target dichroic substance") is measured, and when the polarizer contains two or more types of dichroic substances to be measured, the secondary ion intensity of the fragment derived from the dichroic substance having the greatest absorbance among the target dichroic substances is measured.

[0071] The thickness of the polarizer is not particularly limited, but is preferably from 100 to 8000 nm, and more preferably from 300 to 5000 nm. The thickness of the polarizer refers to the average thickness of the polarizer, which is determined by measuring the thicknesses of the polarizer at any five or more positions and calculating the arithmetic average.

[0072] <Optical anisotropic layer> The optically anisotropic layer is formed using a composition containing a second liquid crystal compound (hereinafter also referred to as a composition for forming an optically anisotropic layer). First, the materials contained in the composition for forming an optically anisotropic layer will be described in detail below.

[0073] (Second liquid crystal compound) The second liquid crystal compound may be any known liquid crystal compound. Generally, liquid crystal compounds can be classified into rod-shaped and disk-shaped types based on their shape. Each type can be further divided into low molecular weight and high molecular weight types. High molecular weight generally refers to those with a degree of polymerization of 100 or more (Polymer Physics, Phase Transition Dynamics, Masao Doi, p. 2, Iwanami Shoten, 1992). The second liquid crystal compound is preferably a rod-shaped liquid crystal compound or a discotic liquid crystal compound, and more preferably a rod-shaped liquid crystal compound.

[0074] As the rod-shaped liquid crystal compound, for example, those described in claim 1 of JP-T-11-513019 or paragraphs

[0026] to

[0098] of JP-A-2005-289980 can be preferably used, and as the discotic liquid crystal compound, for example, those described in paragraphs

[0020] to

[0067] of JP-A-2007-108732 or paragraphs

[0013] to

[0108] of JP-A-2010-244038 can be preferably used, but are not limited thereto.

[0075] The second liquid crystal compound preferably has a polymerizable group. The type of polymerizable group is not particularly limited, and a functional group capable of addition polymerization reaction is preferred, and a polymerizable ethylenically unsaturated group or a ring-polymerizable group is preferred. More specifically, a (meth)acryloyl group, a vinyl group, a styryl group, or an allyl group is preferred, and a (meth)acryloyl group is more preferred. The (meth)acryloyl group is a notation that means a methacryloyl group or an acryloyl group.

[0076] As the second liquid crystal compound, a liquid crystal compound having reverse wavelength dispersion can be used. Here, in this specification, a liquid crystal compound having “reverse wavelength dispersion” refers to a compound that, when a retardation film produced using this compound is measured for its in-plane retardation (Re) value at a specific wavelength (visible light range), the Re value becomes equal or higher as the measured wavelength increases. In addition, the liquid crystal compound with reverse wavelength dispersion is not particularly limited as long as it can form a film with reverse wavelength dispersion as described above, and examples thereof include compounds represented by general formula (1) described in JP2010-084032A (particularly, the compounds described in paragraphs

[0067] to

[0073] ), compounds represented by general formula (II) described in JP2016-053709A (particularly, the compounds described in paragraphs

[0036] to

[0043] ), and compounds represented by general formula (1) described in JP2016-081035A (particularly, the compounds described in paragraphs

[0043] to

[0055] ).

[0077] The absolute value of the difference between the logP of the second liquid crystal compound and the logP of the dichroic material is not particularly limited, but is preferably 3.0 or more, and more preferably 4.0 to 6.0, in terms of better effects of the present invention. When the absolute value of the difference is 3.0 or more, the dichroic material in the polarizer is less likely to migrate to the optically anisotropic layer. When a plurality of dichroic substances are used, it is preferable that the absolute value of the difference between the logP of the second liquid crystal compound and the logP of each of the dichroic substances falls within the above range. When a plurality of second liquid crystal compounds are used, it is preferable that the absolute value of the difference between the logP of each of the second liquid crystal compounds and the logP of the dichroic material falls within the above range. Furthermore, when multiple second liquid crystal compounds and dichroic substances are used, it is preferable that the absolute value of the difference between the logP of each of the multiple combinations of the second liquid crystal compounds and the dichroic substances and the logP of the above-mentioned dichroic substances be within the above range. The logP value is an index expressing the hydrophilic and hydrophobic properties of a chemical structure, and is sometimes called the hydrophilic-hydrophobic parameter. The logP value of each compound can be calculated using software such as ChemBioDraw Ultra or HSPiP (Ver. 4.1.07). It can also be experimentally determined by the method of OECD Guidelines for the Testing of Chemicals, Section 1, Test No. 117, etc. In the present invention, unless otherwise specified, the value calculated by inputting the structural formula of the compound into HSPiP (Ver. 4.1.07) is adopted as the logP value.

[0078] The content of the second liquid crystal compound is preferably 50% by mass or more, more preferably 70% by mass or more, based on the total solid content of the composition for forming an optically anisotropic layer. The upper limit is not particularly limited, but is often 95% by mass or less. Here, "solid content of the composition for forming an optically anisotropic layer" refers to the components excluding the solvent in the composition for forming an optically anisotropic layer, and specific examples of the solid content include the second liquid crystal compound, the polymerization initiator described later, and a surfactant.

[0079] (Other Ingredients) The composition for forming an optically anisotropic layer may contain other components in addition to the second liquid crystal compound. The composition for forming an optically anisotropic layer may contain a polymerization initiator, a surfactant, and a solvent, which may be contained in the composition for forming a polarizer. The content of the polymerization initiator in the composition for forming an optically anisotropic layer is preferably from 0.01 to 20% by mass, more preferably from 0.3 to 10% by mass, based on the total solid content of the composition for forming an optically anisotropic layer.

[0080] The composition for forming an optically anisotropic layer may contain a polymerizable monomer. The polymerizable monomer may be a radically polymerizable or cationic polymerizable compound. Among them, a polyfunctional radically polymerizable monomer is preferable. In addition, the polymerizable monomer may be a monomer copolymerizable with the liquid crystal compound having the above-mentioned polymerizable group. For example, the polymerizable monomer may be the one described in paragraphs

[0018] to

[0020] of JP-A-2002-296423. The content of the polymerizable monomer in the composition for forming an optically anisotropic layer is preferably from 1 to 50% by mass, more preferably from 2 to 30% by mass, based on the total mass of the liquid crystal compound.

[0081] The composition for forming an optically anisotropic layer may contain various alignment control agents such as a vertical alignment agent and a horizontal alignment agent. These alignment control agents are compounds that can control the alignment of a liquid crystal compound horizontally or vertically on the interface side.

[0082] (Method of manufacturing optically anisotropic layer) The method for producing the optically anisotropic layer is not particularly limited, but a method is preferred in which a composition for forming an optically anisotropic layer is applied onto a polarizer to form a coating film, the coating film is subjected to an alignment treatment to align the second liquid crystal compound, and the resulting coating film is subjected to a curing treatment (irradiation with ultraviolet rays (light irradiation treatment) or heat treatment) to form the optically anisotropic layer. As described above, by applying the composition for forming an optically anisotropic layer onto a polarizer, a polarizing plate in which the polarizer and the optically anisotropic layer are disposed adjacent to each other is produced.

[0083] The method for applying the composition for forming an optically anisotropic layer is not particularly limited, and examples thereof include the methods exemplified above as the method for applying the composition for forming a polarizer.

[0084] The treatment for aligning the second liquid crystal compound includes a treatment for drying the coating film at room temperature or a treatment for heating the coating film. In the case of a thermotropic liquid crystal compound, the liquid crystal phase formed by the alignment treatment can generally be transitioned by a change in temperature or pressure. In the case of a lyotropic liquid crystal compound, the transition can also be achieved by a composition ratio such as the amount of solvent. The conditions for heating the coating are not particularly limited, but the heating temperature is preferably 40 to 250° C., more preferably 50 to 150° C., and the heating time is preferably 10 seconds to 10 minutes. After heating the coating film, the coating film may be cooled, if necessary, before the curing treatment (light irradiation treatment) described below. The cooling temperature is preferably 20 to 200°C, and more preferably 30 to 150°C.

[0085] Next, the coating film in which the second liquid crystal compound is aligned is subjected to a curing treatment. The method of hardening treatment performed on the coating film in which the second liquid crystal compound is aligned is not particularly limited, and examples thereof include light irradiation treatment and heat treatment. Among these, from the viewpoint of manufacturability, light irradiation treatment is preferred, and ultraviolet irradiation treatment is more preferred. The irradiation conditions for the light irradiation treatment are not particularly limited, but are preferably 50 to 1000 mJ / cm 2 is preferred.

[0086] (Characteristics of optically anisotropic layer) The thickness of the optically anisotropic layer is not particularly limited, and from the viewpoint of thinning, it is preferably 10 μm or less, more preferably 0.5 to 8.0 μm, and even more preferably 0.5 to 6.0 μm. In this specification, the thickness of the optically anisotropic layer refers to the average thickness of the optically anisotropic layer, which is determined by measuring the thicknesses at any five or more points of the optically anisotropic layer and calculating the arithmetic average of the measured thicknesses.

[0087] The optically anisotropic layer can also be used as a so-called λ / 4 plate or λ / 2 plate by adjusting the in-plane retardation. The λ / 4 plate is a plate that has the function of converting linearly polarized light of a certain wavelength into circularly polarized light (or circularly polarized light into linearly polarized light). More specifically, it is a plate that exhibits an in-plane retardation Re of λ / 4 (or an odd multiple thereof) at a certain wavelength λ nm. The in-plane retardation (Re(550)) of the λ / 4 plate at a wavelength of 550 nm may have an error of about 25 nm around the ideal value (137.5 nm), and is preferably 110 to 160 nm, and more preferably 120 to 150 nm, for example. Moreover, a λ / 2 plate refers to an optically anisotropic film in which the in-plane retardation Re(λ) at a specific wavelength λ nm satisfies Re(λ)≒λ / 2. This formula may be achieved at any wavelength in the visible light range (e.g., 550 nm). In particular, it is preferable that the in-plane retardation Re(550) at a wavelength of 550 nm satisfies the following relationship: 210nm≦Re(550)≦300nm

[0088] The angle between the absorption axis of the polarizer and the in-plane slow axis of the surface of the optically anisotropic layer facing the polarizer is not particularly limited, but is preferably within 1°, more preferably within 0.5°. The lower limit is not particularly limited, but may be 0°. As described later, in an embodiment in which the optically anisotropic layer includes a first optically anisotropic layer and a second optically anisotropic layer, in order to obtain a more excellent effect of the present invention, it is preferable that the angle between the absorption axis of the polarizer and the in-plane slow axis on the polarizer-side surface of the first optically anisotropic layer is within the above range. The direction of the absorption axis of the polarizer and the direction of the in-plane slow axis of the optically anisotropic layer are measured using an Axoscan (polarimeter) device manufactured by Axometrics and analysis software from the same company.

[0089] The optically anisotropic layer may be a layer in which a second liquid crystal compound is fixed in a twisted alignment with the thickness direction as the helical axis, or a layer in which a second liquid crystal compound is fixed in a horizontal alignment. Among these, in terms of superior effects of the present invention, a layer in which a second liquid crystal compound is fixed and helically aligned with the thickness direction as the helical axis is preferable. The twist angle of the second liquid crystal compound is not particularly limited, but is preferably more than 0° and less than 360°. The "fixed" state is a state in which the alignment of the liquid crystal compound is maintained. Specifically, it is preferable that the layer has no fluidity in a temperature range of usually 0 to 50° C., or under more severe conditions, −30 to 70° C., and that the alignment state is not changed by an external field or external force, and the fixed alignment state can be stably maintained.

[0090] The optically anisotropic layer may be composed of a single layer or may have multiple layers, that is, the optically anisotropic layer may have multiple layers in which the second liquid crystal compound is fixed and twisted in a helical axis along the thickness direction. The optically anisotropic layer is preferably composed of a plurality of layers each having a different twist angle of the second liquid crystal compound. It is preferable that the second liquid crystal compound in each of the plurality of layers has a different twist angle. Moreover, the plurality of layers preferably have different ratios of the twist angle of the second liquid crystal compound to the layer thickness (twist angle of the second liquid crystal compound (°) / layer thickness (μm)).

[0091] <Preferred embodiment of polarizing plate> One of the preferred embodiments of the polarizer is an embodiment in which the optically anisotropic layer has a first optically anisotropic layer and a second optically anisotropic layer, which will be described later. 3, the polarizing plate 10B has a polarizer 12 and an optically anisotropic layer 140, and the optically anisotropic layer 140 has a first optically anisotropic layer 16 and a second optically anisotropic layer 18. In the optically anisotropic layer 140, the first optically anisotropic layer 16 is disposed closer to the polarizer 12 than the second optically anisotropic layer 18. The polarizer 12 is the same as the polarizer 12 shown in FIG. 1 described above, and a description thereof will be omitted. In the following, the first optically anisotropic layer 16 and the second optically anisotropic layer 18 will be mainly described in detail.

[0092] (First optically anisotropic layer) The first optically anisotropic layer is a layer in which a second liquid crystal compound is fixed in a twisted orientation with the thickness direction (z-axis direction in FIG. 3) as the helical axis. The first optically anisotropic layer is preferably a layer in which a chiral nematic phase having a so-called helical structure is fixed. When forming the above phase, it is preferable to use a mixture of a second liquid crystal compound exhibiting a nematic liquid crystal phase and a chiral agent described later. The meaning of the "fixed" state is as described above.

[0093] The twist angle of the second liquid crystal compound in the first optically anisotropic layer is 26.5±10.0°, more preferably 26.5±8.0°, and even more preferably 26.5±6.0°, in terms of better effects of the present invention. In this specification, the torsion angle is measured using an Axoscan (polarimeter) device manufactured by Axometrics and analysis software from the same company. The twisted alignment of the second liquid crystal compound means that the second liquid crystal compound is twisted from one main surface to the other main surface of the first optically anisotropic layer around the thickness direction of the first optically anisotropic layer as an axis, and accordingly, the alignment direction (in-plane slow axis direction) of the second liquid crystal compound varies depending on the position in the thickness direction of the first optically anisotropic layer.

[0094] The second liquid crystal compound in the first optically anisotropic layer may have two twist directions, either right-handed or left-handed. In Fig. 3, right-handed twist refers to a right-handed twist (clockwise twist) when observed from the second optically anisotropic layer toward the first optically anisotropic layer.

[0095] The value of the product Δn1·d1 of the refractive index anisotropy Δn1 of the first optically anisotropic layer measured at a wavelength of 550 nm and the thickness d1 of the first optically anisotropic layer satisfies the following formula (1). Formula (1) 252nm≦Δn1·d1≦312nm Among these, in terms of obtaining superior effects of the present invention, it is preferable that formula (1A) is satisfied, and it is more preferable that formula (1B) is satisfied. Formula (1A) 262nm≦Δn1·d1≦302nm Formula (1B) 272nm≦Δn1·d1≦292nm The measurement method for Δn1·d1 is the same as the measurement method for the torsion angle, and is performed using an Axoscan (polarimeter) device from Axometrics and analysis software from the same company.

[0096] (Second optically anisotropic layer) The second optically anisotropic layer, like the first optically anisotropic layer, is a layer formed by fixing second rod-shaped liquid crystal compounds helically aligned with the thickness direction (z-axis direction in FIG. 3) as the helical axis. The twist angle of the second liquid crystal compound is 78.6±10.0°, and from the viewpoint of obtaining a better effect of the present invention, 78.6±8.0° is more preferable, and 78.6±6.0° is even more preferable. The twist direction of the second liquid crystal compound in the second optically anisotropic layer is the same as that of the second liquid crystal compound in the first optically anisotropic layer described above. For example, if the twist direction of the second liquid crystal compound in the first optically anisotropic layer is right-handed, the twist direction of the second liquid crystal compound in the second optically anisotropic layer is also right-handed.

[0097] The value of the product Δn2·d2 of the refractive index anisotropy Δn2 of the second optically anisotropic layer measured at a wavelength of 550 nm and the thickness d2 of the second optically anisotropic layer satisfies the following formula (2). Formula (2) 110nm≦Δn2·d2≦170nm Among these, in terms of obtaining superior effects of the present invention, it is preferable that formula (2A) is satisfied, and it is even more preferable that formula (2B) is satisfied. Formula (2A) 120nm≦Δn2·d2≦160nm Formula (2B) 130nm≦Δn2·d2≦150nm The measurement method for Δn2·d2 is the same as the measurement method for the torsion angle, and is performed using an Axoscan (polarimeter) device from Axometrics and analysis software from the same company.

[0098] The in-plane slow axis of the first optically anisotropic layer on the surface facing the second optically anisotropic layer is arranged parallel to the in-plane slow axis of the second optically anisotropic layer on the surface facing the first optically anisotropic layer. The definition of "parallel" is as described above.

[0099] (Angle relationship) The absorption axis of the polarizer is parallel to the in-plane slow axis of the first optically anisotropic layer on the surface facing the polarizing film. The relationship between the absorption axis of the polarizer, the in-plane slow axis of the first optically anisotropic layer, and the in-plane slow axis of the second optically anisotropic layer will be described in more detail with reference to FIG. The arrow in the polarizer 12 in Fig. 4 indicates the absorption axis, and the arrows in the first optically anisotropic layer 16 and the second optically anisotropic layer 18 indicate the in-plane slow axis in each layer. Fig. 5 shows the relationship between the absorption axis of the polarizer 12, the in-plane slow axis of the first optically anisotropic layer 16, and the in-plane slow axis of the second optically anisotropic layer 18 when observed from the white arrow in Fig. 4. In FIG. 5, the rotation angle of the in-plane slow axis is expressed as a positive value in the counterclockwise direction and a negative value in the clockwise direction with respect to the absorption axis of the polarizer 12 when observed from the white arrow in FIG.

[0100] 4, the absorption axis of the polarizer 12 is parallel to the in-plane slow axis of the surface 16a of the first optically anisotropic layer 16 facing the polarizer 12. The definition of "parallel" is as described above. As described above, the first optically anisotropic layer 16 is a layer in which the second liquid crystal compound is fixed and twisted with the thickness direction as the helical axis. Therefore, as shown in FIG. 4, the in-plane slow axis at the surface 16a of the first optically anisotropic layer 16 on the polarizer 12 side and the in-plane slow axis at the surface 16b of the first optically anisotropic layer 16 on the second optically anisotropic layer 18 side form the above-mentioned twist angle (26.5° in FIG. 4). That is, the in-plane slow axis of the first optically anisotropic layer 16 rotates by −26.5° (26.5° clockwise). Therefore, the angle φ2 between the absorption axis of the polarizer 12 and the in-plane slow axis at the surface 16b of the first optically anisotropic layer 16 is 26.5°. In addition, in Figure 5, the in-plane slow axis at surface 16b of the first optical anisotropic layer 16 is shown rotated 26.5° clockwise relative to the in-plane slow axis at surface 16a of the first optical anisotropic layer 16, but this is not limited to this embodiment, and the rotation angle may be in the range of 26.5±10° clockwise.

[0101] 4, the in-plane slow axis of the first optically anisotropic layer 16 at the surface 16b facing the second optically anisotropic layer 18 is parallel to the in-plane slow axis of the second optically anisotropic layer 18 at the surface 18a facing the first optically anisotropic layer 16. In other words, the angle φ3 between the absorption axis of the polarizer 12 and the in-plane slow axis of the second optically anisotropic layer 18 at the surface 18a facing the first optically anisotropic layer 16 is approximately the same as the angle φ2b.

[0102] As described above, the second optically anisotropic layer 18 is a layer in which a liquid crystal compound is fixed that is twisted and aligned with the thickness direction as the helical axis. Therefore, as shown in FIG. 4, the in-plane slow axis of the second optically anisotropic layer 18 at the surface 18a on the first optically anisotropic layer 16 side and the in-plane slow axis of the second optically anisotropic layer 18 at the surface 18b opposite to the first optically anisotropic layer 16 side form the above-mentioned twist angle (78.6° in FIG. 4). That is, the in-plane slow axis of the second optically anisotropic layer 18 rotates by −78.6° (78.6° clockwise). Therefore, the angle φ4 between the absorption axis of the polarizer 12 and the in-plane slow axis of the surface 18b of the second optically anisotropic layer 18 is 105.1°. In addition, in Figure 4, the in-plane slow axis at surface 18b of the second optical anisotropic layer 18 is shown rotated 78.6° clockwise relative to the in-plane slow axis at surface 18a of the second optical anisotropic layer 18, but this is not limited to this embodiment, and the rotation angle may be in the range of -78.6±10° clockwise.

[0103] As described above, in the embodiment of FIG. 4, the twist directions of the second liquid crystal compounds in the first optically anisotropic layer 16 and the second optically anisotropic layer 18 both show a clockwise (right-handed) twist with respect to the absorption axis of the polarizer 12. Although an embodiment in which the twist direction is clockwise (right twist) has been described in detail with reference to FIG. 4, the twist directions of the second liquid crystal compound in the first optically anisotropic layer 16 and the second optically anisotropic layer 18 may both be counterclockwise.

[0104] (Preferred embodiment of the manufacturing method) A preferred embodiment of a method for producing an optically anisotropic layer including a first optically anisotropic layer and a second optically anisotropic layer is not particularly limited, but may involve the following steps 1 to 5. By carrying out the following steps 1 to 5, an optically anisotropic layer including a first optically anisotropic layer and a second optically anisotropic layer can be produced in a single coating step. Step 1: A step of applying a polymerizable liquid crystal composition containing a chiral agent including at least a photosensitive chiral agent whose helical twisting power changes upon irradiation with light, and a liquid crystal compound having a polymerizable group (hereinafter, in the explanation of steps 1 to 5, this is also simply referred to as a "liquid crystal compound") onto a polarizer to form a composition layer. Step 2: A step of subjecting the composition layer to a heat treatment to cause the liquid crystal compound in the composition layer to be twisted and aligned along a helical axis extending in the thickness direction. Step 3: After step 2, a step of irradiating the composition layer with light under conditions of an oxygen concentration of 1% by volume or more. Step 4: After step 3, a step of subjecting the composition layer to a heat treatment. Step 5: After step 4, the composition layer is subjected to a curing treatment to fix the alignment state of the liquid crystal compound and form a first optically anisotropic layer and a second optically anisotropic layer. The procedures for each of the above steps will be described in detail below.

[0105] [Process 1] In step 1, a polymerizable liquid crystal composition containing a chiral agent including at least a photosensitive chiral agent whose helical twisting power changes upon irradiation with light and a liquid crystal compound having a polymerizable group is applied onto a polarizer to form a composition layer. By carrying out this step, a composition layer to be subjected to the light irradiation treatment described later is formed. The various components contained in the polymerizable liquid crystal composition include the components that can be contained in the composition for forming an optically anisotropic layer described above, and the photosensitive chiral agent not described above will be described in detail below. The helical twisting power (HTP) of a chiral agent is a factor indicating the helical orientation ability represented by the following formula (X). Formula (X) HTP = 1 / (helix pitch length (unit: μm) × concentration of chiral agent relative to liquid crystal compound (mass%)) [μm -1 ] The helical pitch length refers to the length of the pitch P (=helical period) of the helical structure of a cholesteric liquid crystal phase, and can be measured by the method described on page 196 of Liquid Crystal Handbook (published by Maruzen Co., Ltd.).

[0106] The photosensitive chiral agent (hereinafter, simply referred to as "chiral agent A") whose helical twisting power changes upon irradiation with light may be liquid crystalline or non-liquid crystalline. Generally, chiral agent A often contains an asymmetric carbon atom. Note that chiral agent A may be an axially asymmetric compound or a planar asymmetric compound that does not contain an asymmetric carbon atom. The chiral agent A may have a polymerizable group.

[0107] The chiral agent A may be a chiral agent whose helical twisting power increases or decreases upon irradiation with light, and is preferably a chiral agent whose helical twisting power decreases upon irradiation with light. In this specification, "increase and decrease in helical twisting power" refers to an increase or decrease when the initial helical direction (before light irradiation) of the chiral agent A is taken as "positive." Therefore, even when the helical twisting power continues to decrease upon light irradiation and exceeds 0, causing the helical direction to become "negative" (i.e., when a helical direction opposite to the initial helical direction (before light irradiation) is induced), this also corresponds to "a chiral agent whose helical twisting power decreases."

[0108] An example of the chiral agent A is a so-called photoreactive chiral agent. The photoreactive chiral agent has a chiral moiety and a photoreactive moiety that undergoes a structural change upon irradiation with light, and is a compound that, for example, significantly changes the twisting power of a liquid crystal compound depending on the amount of irradiation. Among them, the chiral agent A is preferably a compound having at least a photoisomerization site, and more preferably the photoisomerization site has a photoisomerizable double bond. As the photoisomerization site having the photoisomerizable double bond, a cinnamoyl site, a chalcone site, an azobenzene site, or a stilbene site is preferable because photoisomerization is easily caused and the difference in helical induction power before and after light irradiation is large, and a cinnamoyl site, a chalcone site, or a stilbene site is more preferable because the absorption of visible light is small. The photoisomerization site corresponds to the photoreactive site whose structure changes by light irradiation described above.

[0109] The chiral agent A is preferably a compound represented by formula (C). Formula (C) RLR Each R independently represents a group having at least one moiety selected from the group consisting of a cinnamoyl moiety, a chalcone moiety, an azobenzene moiety, and a stilbene moiety. L represents a divalent linking group formed by removing two hydrogen atoms from the structure represented by formula (D) (a divalent linking group formed by removing two hydrogen atoms from the binaphthyl partial structure), a divalent linking group represented by formula (E) (a divalent linking group consisting of the isosorbide partial structure), or a divalent linking group represented by formula (F) (a divalent linking group consisting of the isomannide partial structure). In formula (E) and formula (F), * represents a bonding position.

[0110] [ka]

[0111] At least the above-mentioned chiral agent A is used in step 1. Step 1 may be an embodiment in which two or more types of chiral agents A are used, or may be an embodiment in which at least one type of chiral agent A and at least one type of chiral agent whose helical twisting power does not change upon irradiation with light (hereinafter, also simply referred to as "chiral agent B") are used. The chiral agent B may be liquid crystal or non-liquid crystal. The chiral agent B generally contains an asymmetric carbon atom. The chiral agent B may be an axially asymmetric compound or a planar asymmetric compound that does not contain an asymmetric carbon atom. The chiral agent B may have a polymerizable group. As the chiral agent B, a known chiral agent can be used. Chiral agent B is preferably a chiral agent that induces a helical twist in the opposite direction to that of the above-mentioned chiral agent A. That is, for example, when the helical twist induced by chiral agent A is right-handed, the helical twist induced by chiral agent B is left-handed.

[0112] The content of the chiral agent A in the composition layer is not particularly limited, but in order to facilitate uniform alignment of the liquid crystal compound, it is preferably 5.0% by mass or less, more preferably 3.0% by mass or less, even more preferably 2.0% by mass or less, particularly preferably less than 1.0% by mass, more particularly preferably 0.8% by mass or less, and most preferably 0.5% by mass or less, relative to the total mass of the liquid crystal compound. The lower limit is not particularly limited, but is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, and even more preferably 0.05% by mass or more. The chiral agent A may be used alone or in combination of two or more. When two or more chiral agents A are used in combination, the total content is preferably within the above range.

[0113] The content of the chiral agent B in the composition layer is not particularly limited, but in terms of facilitating uniform alignment of the liquid crystal compound, it is preferably 5.0% by mass or less, more preferably 3.0% by mass or less, even more preferably 2.0% by mass or less, particularly preferably less than 1.0% by mass, more particularly preferably 0.8% by mass or less, and most preferably 0.5% by mass or less, relative to the total mass of the liquid crystal compound. The lower limit is not particularly limited, but it is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, and even more preferably 0.05% by mass or more. The chiral agent B may be used alone or in combination of two or more. When two or more chiral agents B are used in combination, the total content is preferably within the above range.

[0114] The total content of the chiral dopant in the composition layer (total content of all chiral dopant) is preferably 5.0% by mass or less, more preferably 4.0% by mass or less, even more preferably 2.0% by mass or less, and particularly preferably 1.0% by mass or less, based on the total mass of the liquid crystal compound. There is no particular lower limit, but it is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, and even more preferably 0.05% by mass or more.

[0115] The method for forming a composition layer by applying the polymerizable liquid crystal composition is not particularly limited, and examples thereof include the method for applying the above-mentioned polarizer-forming composition.

[0116] The thickness of the composition layer is not particularly limited, but is preferably from 0.1 to 20 μm, more preferably from 0.2 to 15 μm, and even more preferably from 0.5 to 10 μm.

[0117] (Process 2) Step 2 is a step of subjecting the composition layer to a heat treatment to cause the polymerizable liquid crystal compound in the composition layer to be twisted and aligned along a helical axis extending in the thickness direction. The optimum conditions for the heat treatment are selected depending on the liquid crystal compound used. Among these, the heating temperature is often 10 to 250°C, more often 40 to 150°C, and even more often 50 to 130°C. The heating time is often 0.1 to 60 minutes, and more often 0.2 to 5 minutes.

[0118] The absolute value of the weighted average helical twisting power of the chiral agent in the composition layer formed in step 1 is 0 μm -1 More preferably, it is greater than 0 μm. -1 Ultra 1.9μm -1 More preferably, it is 0 μm or less. -1 Ultra 1.5μm -1 More preferably, it is 0.00 μm or less. -1 Ultra 1.0μm -1 It is particularly preferred that:

[0119] The weighted average helical twisting power of the chiral agent means, when two or more kinds of chiral agents are contained in the composition layer, the sum of the product of the helical twisting power of each chiral agent contained in the composition layer and the concentration (mass%) of each chiral agent in the composition layer divided by the total concentration (mass%) of the chiral agents in the composition layer. For example, when two kinds of chiral agents (chiral agent X and chiral agent Y) are used in combination, it is represented by the following formula (Y). Equation (Y) Weighted average helical induced force (μm -1 )=(helix-inducing power of chiral agent X (μm -1 ) × concentration of chiral dopant X in the composition layer (% by mass) + helical twisting power of chiral dopant Y (μm -1 ) × concentration of chiral agent Y in the composition layer (mass%) / (concentration of chiral agent X in the composition layer (mass%) + concentration of chiral agent Y in the composition layer (mass%)) However, in the above formula (Y), when the helical direction of the chiral agent is right-handed, the helical twisting power is a positive value. On the other hand, when the helical direction of the chiral agent is left-handed, the helical twisting power is a negative value. That is, for example, when the helical twisting power is 10 μm -1 In the case of the chiral agent, when the helical direction of the helix induced by the chiral agent is right-handed, the helical induction force is 10 μm -1 On the other hand, when the helical direction of the helix induced by the chiral agent is left-handed, the helical induction force is expressed as -10 μm -1 It is expressed as:

[0120] The absolute value of the weighted average helical twisting power of the chiral agent in the composition layer formed by step 1 is 0 μm -1 When the thickness is greater than 100 nm, as shown in FIG. 6, a composition layer 20 is formed on the polarizer 12 in which the liquid crystal compound LC is twisted and aligned along a helical axis extending in the thickness direction. Fig. 6 is a schematic diagram of a cross section of the polarizer 12 and the composition layer 20. Chiral agents A and B are present in the composition layer 20 shown in Fig. 6, the concentration of the chiral agent B is greater than that of the chiral agent A, the helical direction induced by the chiral agent A is left-handed, and the helical direction induced by the chiral agent B is right-handed. In addition, the absolute value of the helical twisting power of the chiral agent A and the absolute value of the helical twisting power of the chiral agent B are the same.

[0121] (Step 3) Step 3 is a step of irradiating the composition layer with light in the presence of oxygen after step 2. The mechanism of this step will be described below with reference to the drawings. 7, in the above-mentioned step 2, light irradiation is performed from the direction opposite to the composition layer 20 side of the polarizer 12 (the direction of the white arrow in FIG. 7) under the condition of an oxygen concentration of 1% by volume or more. Note that although light irradiation is performed from the polarizer 12 side in FIG. 7, it may be performed from the composition layer 20 side. In this case, when comparing the first region 20A on the polarizer 12 side of the composition layer 20 with the second region 20B on the opposite side to the polarizer 12 side, the surface of the second region 20B is on the air side, so the oxygen concentration in the second region 20B is high and the oxygen concentration in the first region 20A is low. Therefore, when the composition layer 20 is irradiated with light, polymerization of the liquid crystal compound is likely to proceed in the first region 20A, and the alignment state of the liquid crystal compound is fixed. Note that the chiral agent A is also present in the first region 20A, and the chiral agent A is also photosensitive, and the helical induction force changes. However, since the alignment state of the liquid crystal compound is fixed in the first region 20A, even if step 4, which will be described later, is performed to perform a heat treatment on the light-irradiated composition layer, the alignment state of the liquid crystal compound does not change. In addition, since the oxygen concentration is high in the second region 20B, even if light is irradiated, the polymerization of the liquid crystal compound is inhibited by oxygen, and the polymerization does not proceed easily. Since the chiral agent A is also present in the second region 20B, the chiral agent A is exposed to light and the helical twisting power changes. Therefore, when step 4 (heat treatment) described later is performed, the alignment state of the liquid crystal compound changes according to the changed helical twisting power.

[0122] That is, by carrying out step 3, the alignment state of the liquid crystal compound is easily fixed in the region of the composition layer on the polarizer side, whereas the alignment state of the liquid crystal compound is less likely to be solidified in the region of the composition layer opposite the polarizer side, resulting in a state in which the helical twisting power changes depending on the photoexposed chiral dopant A.

[0123] Step 3 is carried out under conditions of an oxygen concentration of 1% by volume or more. In particular, the oxygen concentration is preferably 2% by volume or more, more preferably 5% by volume or more, in that regions in which the alignment state of the liquid crystal compound is different are easily formed in the optically anisotropic layer. The upper limit is not particularly limited, but may be 100% by volume.

[0124] The irradiation intensity of the light irradiation in step 3 is not particularly limited and can be appropriately determined based on the helical twisting power of the chiral agent A. The irradiation amount of the light irradiation in step 3 is not particularly limited, but it is preferably 300 mJ / cm from the viewpoint of facilitating the formation of a desired optically anisotropic layer. 2 Less than 200 mJ / cm is preferable. 2 The lower limit is 5 mJ / cm2, which is more preferable because it is easy to form a desired optically anisotropic layer. 2 More than 10 mJ / cm is preferable. 2 The above is more preferable. The light irradiation in step 3 is preferably carried out at a temperature of 15 to 70°C (preferably 15 to 50°C).

[0125] The light used for the photoirradiation may be any light to which the chiral agent A is photosensitive. In other words, the light used for the photoirradiation is not particularly limited as long as it is an actinic ray or radiation that changes the helical twisting power of the chiral agent A, and examples of the light include the bright line spectrum of a mercury lamp, far ultraviolet light represented by an excimer laser, extreme ultraviolet light, X-rays, ultraviolet light, and electron beams. Among these, ultraviolet light is preferred.

[0126] (Step 4) Step 4 is a step of subjecting the composition layer to a heat treatment after step 3. By carrying out this step, the alignment state of the liquid crystal compound is changed in a region in the composition layer irradiated with light where the helical twisting power of the chiral dopant A has been changed. The mechanism of this process will be explained below with reference to the drawings.

[0127] As described above, when step 3 is performed on the composition layer 20 shown in FIG. 7, the orientation state of the liquid crystal compound is fixed in the first region 20A, whereas the polymerization of the liquid crystal compound is difficult to proceed in the second region 20B, and the orientation state of the liquid crystal compound is not fixed. Moreover, the helical twisting power of the chiral agent A changes in the second region 20B. When such a change in the helical twisting power of the chiral agent A occurs, the force twisting the liquid crystal compound in the second region 20B changes compared to the state before light irradiation. This point will be explained in more detail. As described above, chiral agents A and B are present in the composition layer 20 shown in Fig. 6, the concentration of chiral agent B is greater than that of chiral agent A, the helical direction induced by chiral agent A is left-handed, and the helical direction induced by chiral agent B is right-handed. Furthermore, the absolute value of the helical twisting power of chiral agent A is the same as that of chiral agent B. Therefore, the weighted average helical twisting power of the chiral agents in the composition layer before light irradiation exhibits a positive value. The above embodiment is shown in Figure 8. In Figure 8, the vertical axis indicates the helical twisting power of the chiral agent (μm -1 The horizontal axis represents "light irradiation dose (mJ / cm ) × concentration of chiral agent (mass%)", and the further away from zero the value is, the stronger the helical twisting power is. 2 )". First, the relationship between chiral agent A and chiral agent B in the composition layer before light irradiation corresponds to the time when the amount of light irradiation is 0, and the "helix induction power of chiral agent A (μm -1 ) × concentration of chiral agent A (mass%) and the helical twisting power of chiral agent B (μm -1 ) × concentration of chiral agent B (mass%)” is compared with the absolute value of “helix induction power of chiral agent B (μm -1 ) × concentration of chiral dopant B (mass%) is larger. In other words, a helical induction force is generated in the helical direction (+) induced by chiral dopant B. Therefore, as shown in Figure 6, the liquid crystal compound is twisted and aligned along the thickness direction. When light is irradiated to second region 20B in this state, and the helical twisting power of chiral agent A decreases depending on the amount of light irradiation as shown in Fig. 8, the weighted average helical twisting power of the chiral agent in second region 20B increases, and the right-handed helical twisting power becomes stronger, as shown in Fig. 9. In other words, the helical twisting power of the liquid crystal compound increases in the direction (+) of the helical twist induced by chiral agent B as the amount of irradiation increases. Therefore, when the composition layer 20 after step 3, in which such a change in the weighted average helical twisting force has occurred, is subjected to a heat treatment to promote reorientation of the liquid crystal compound, as shown in Figure 10, in the second region 20B, the twist angle of the liquid crystal compound LC increases along the helical axis extending along the thickness direction of the composition layer 20. On the other hand, as described above, in the first region 20A of the composition layer 20, the polymerization of the liquid crystal compound has progressed during step 3, and the orientation state of the liquid crystal compound has been fixed, so that reorientation of the liquid crystal compound does not proceed. As described above, by carrying out step 4, a plurality of regions in which the liquid crystal compound has a different alignment state are formed along the thickness direction of the composition layer. The degree of twist of the liquid crystal compound LC can be appropriately adjusted by the type of chiral dopant A used, the exposure dose in step 3, and the like, to achieve a desired twist angle.

[0128] In the above, the embodiment in which a chiral agent whose helical twisting power decreases upon irradiation with light is used as the chiral agent A has been described, but the present invention is not limited to this embodiment. For example, a chiral agent whose helical twisting power increases upon irradiation with light may be used as the chiral agent A. In this case, the helical twisting power induced by the chiral agent A increases upon irradiation with light, and the liquid crystal compound is twisted in the direction of rotation induced by the chiral agent A. In addition, in the above, the embodiment in which the chiral agent A and the chiral agent B are used in combination has been described, but the present invention is not limited to this embodiment. For example, the present invention may be an embodiment in which two types of chiral agents A are used. Specifically, the present invention may be an embodiment in which a chiral agent A1 that induces left-handedness and a chiral agent A2 that induces right-handedness are used in combination. The chiral agents A1 and A2 may each independently be a chiral agent that increases the helical induction power, or a chiral agent that decreases the helical induction power. For example, a chiral agent that induces left-handedness and whose helical induction power increases upon light irradiation and a chiral agent that induces right-handedness and whose helical induction power decreases upon light irradiation may be used in combination.

[0129] The optimum conditions for the heat treatment are selected depending on the liquid crystal compound used. Among these, the heating temperature is preferably the temperature to which the material is heated from the state in step 3, which is often 35 to 250°C, more often 50 to 150°C, even more often higher than 50°C and up to 150°C, and particularly often 60 to 130°C. The heating time is often 0.01 to 60 minutes, and more often 0.03 to 5 minutes.

[0130] The absolute value of the weighted average helical twisting power of the chiral agent in the composition layer after light irradiation is not particularly limited, but the absolute value of the difference between the weighted average helical twisting power of the chiral agent in the composition layer after light irradiation and the weighted average helical twisting power before light irradiation is 0.05 μm -1 More than this is preferable, and 0.05 to 10.0 μm -1 More preferably, 0.1 to 10.0 μm -1 is more preferred.

[0131] (Step 5) Step 5 is a step of forming a first optically anisotropic layer and a second optically anisotropic layer by subjecting the composition layer to a curing treatment after step 4 to fix the alignment state of the liquid crystal compound. By carrying out this step, the alignment state of the liquid crystal compound in the composition layer is fixed, and as a result, a predetermined optically anisotropic layer is formed.

[0132] The method of the curing treatment is not particularly limited, and examples thereof include photocuring treatment and heat curing treatment. Among them, photoirradiation treatment is preferred, and ultraviolet irradiation treatment is more preferred. For ultraviolet irradiation, a light source such as an ultraviolet lamp is used. The amount of light (e.g., ultraviolet light) applied is not particularly limited, but is generally 100 to 800 mJ / cm 2 degree is preferred.

[0133] <Other materials> The polarizing plate of the present invention may have other members in addition to the above-mentioned polarizer and optically anisotropic layer.

[0134] (Support) The polarizing plate may have a support. As described above, the support is included as an object to be coated with the polarizer-forming composition, and may be included in the polarizing plate as it is.

[0135] The support is preferably a transparent support, which means a support having a visible light transmittance of 60% or more, preferably 80% or more, and more preferably 90% or more.

[0136] The support may be a long support (long support). The length of the long support in the longitudinal direction is not particularly limited, but a support of 10 m or more is preferable, and from the viewpoint of productivity, a support of 100 m or more is preferable. The length in the longitudinal direction is not particularly limited, and is often 10,000 m or less. The width of the long support is not particularly limited, but is often 150 to 3000 mm, preferably 300 to 2000 mm.

[0137] The support may contain various additives (for example, an optical anisotropy adjusting agent, a wavelength dispersion adjusting agent, fine particles, a plasticizer, an ultraviolet protection agent, a deterioration inhibitor, and a release agent).

[0138] The support may be subjected to a surface treatment (e.g., glow discharge treatment, corona discharge treatment, ultraviolet (UV) treatment, and flame treatment) on the surface thereof to improve adhesion with a layer disposed thereon. In addition, an adhesive layer (undercoat layer) may be provided on the support. The support may be a so-called temporary support.

[0139] In addition, the surface of the support may be directly subjected to rubbing treatment. In other words, a support that has been subjected to rubbing treatment may be used. The direction of the rubbing treatment is not particularly limited, and an optimal direction is appropriately selected depending on the direction in which the liquid crystal compound is desired to be aligned. The rubbing treatment can be a treatment method that is widely used as a liquid crystal alignment treatment process for LCDs (liquid crystal displays), in which the surface of the support is rubbed in a certain direction with paper, gauze, felt, rubber, nylon fiber, polyester fiber, or the like to obtain alignment. As described above, the support may have an alignment layer on its surface.

[0140] (Surface protective layer) The polarizing plate may have a surface protective layer. When the polarizing plate is applied to an image display device, this surface protective layer is preferably disposed on the most visible side. The material constituting the surface protective layer is not particularly limited, and may be an inorganic or organic material. Examples of the surface protective layer include a glass substrate and a polymer film such as a polyimide or cellulose acylate film. The surface layer of the surface protective layer may include one or more layers selected from a surface-hardening layer (hard coat layer) and a low-reflection layer that suppresses surface reflection occurring at the air interface. Alternatively, a polarizer may be formed by directly applying a polarizer-forming composition to the surface of the surface protective layer opposite to the viewing side.

[0141] The thickness of the surface protective layer is not particularly limited, but is preferably 800 μm or less, more preferably 100 μm or less, from the viewpoint of thinning. The lower limit is not particularly limited, but is preferably 0.1 μm or more. For example, a bendable glass substrate having a thickness of 100 μm or less is preferable because it makes it possible to take advantage of the flexible characteristics of the organic EL display device. Furthermore, for glass substrates having a thickness of 100 μm or less, from the viewpoint of impact resistance, it is also preferable to laminate a resin film of a (meth)acrylic resin, a polyester resin such as polyethylene terephthalate (PET), a cellulose resin such as triacetyl cellulose (TAC), or a cycloolefin resin such as norbornene resin, as a protective film, to the glass substrate with an adhesive, etc. In particular, from the viewpoint of flexibility, it is preferable to laminate polyethylene terephthalate (PET) to the glass substrate, and furthermore, from the viewpoint of visibility, polyethylene terephthalate (PET) having an in-plane retardation of 3000 to 10000 nm is preferable.

[0142] <Organic EL (electroluminescence) display device> The organic EL display device of the present invention has the above-mentioned polarizing plate. The polarizing plate of the present invention can be suitably used as a circular polarizing plate. Typically, a polarizing plate is provided on an organic EL display panel (organic EL display element) of an organic EL display device. In the polarizing plate, a polarizer is disposed on the viewing side.

[0143] An organic EL display panel is a member in which a light-emitting layer or a plurality of organic compound thin films including a light-emitting layer are formed between a pair of electrodes, an anode and a cathode, and may have a hole injection layer, a hole transport layer, an electron injection layer, an electron transport layer, a protective layer, etc. in addition to the light-emitting layer, and each of these layers may have other functions. Various materials can be used to form each layer. EXAMPLES

[0144] The features of the present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts, ratios, processing contents, and processing procedures shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below.

[0145] <Example 1> (Preparation of transparent support) The following composition was charged into a mixing tank and stirred to prepare a cellulose acetate solution to be used as a cellulose acylate dope for the core layer. ------------------------------------------------------------------ Core layer: Cellulose acylate dope ------------------------------------------------------------------ Cellulose acetate with an acetyl substitution degree of 2.88: 100 parts by weight In the embodiment of JP 2015-227955 A 12 parts by weight of the polyester compound B 2 parts by weight of the following compound F Methylene chloride (first solvent) 430 parts by weight Methanol (second solvent) 64 parts by weight ------------------------------------------------------------------

[0146] Compound F

[0147] [ka]

[0148] To 90 parts by weight of the above-mentioned cellulose acylate dope for the core layer, 10 parts by weight of the following matting agent solution was added to prepare a cellulose acetate solution to be used as the cellulose acylate dope for the outer layer.

[0149] ------------------------------------------------------------------ Matting agent solution ------------------------------------------------------------------ Silica particles with an average particle size of 20 nm (AEROSIL R972, manufactured by Nippon Aerosil Co., Ltd.) 2 parts by weight Methylene chloride (first solvent) 76 parts by weight Methanol (second solvent) 11 parts by weight 1 part by weight of the above-mentioned cellulose acylate dope for the core layer ------------------------------------------------------------------

[0150] The above core layer cellulose acylate dope and the above outer layer cellulose acylate dope were filtered through a filter paper with an average pore size of 34 μm and a sintered metal filter with an average pore size of 10 μm, and then the above core layer cellulose acylate dope and the outer layer cellulose acylate dope on both sides were simultaneously cast onto a drum at 20°C from a casting nozzle (band casting machine). Next, when the solvent content in the film was about 20% by mass, the film was peeled off from the drum, both ends in the width direction of the film were fixed with tenter clips, and the film was stretched in the transverse direction at a stretch ratio of 1.1 times while being dried. Thereafter, the obtained film was further dried by conveying it between rolls of a heat treatment device to prepare a transparent support having a thickness of 40 μm, which was designated as cellulose acylate film A1.

[0151] (Formation of photo-alignment film B1) A composition for forming a photo-alignment film, which will be described later, was continuously applied onto the cellulose acylate film A1 using a wire bar. The support on which the coating film was formed was dried with hot air at 140° C. for 120 seconds, and then the coating film was irradiated with polarized ultraviolet light (10 mJ / cm 2 A photo-alignment film was formed by irradiating the liquid crystal with a super-high pressure mercury lamp, and a TAC (triacetyl cellulose) film with a photo-alignment film was obtained. The thickness of the photo-alignment film was 0.25 μm. ------------------------------------------------------------------ Composition for forming photo-alignment film ------------------------------------------------------------------ 100.00 parts by weight of the following polymer PA-1 8.25 parts by weight of the following acid generator PAG-1 - 0.6 parts by weight of the following stabilizer DIPEA Xylene 1126.60 parts by weight Methyl isobutyl ketone 125.18 parts by weight ------------------------------------------------------------------

[0152] Polymer PA-1 (wherein the numerical value for each repeating unit represents the content (mass%) of each repeating unit relative to all repeating units.)

[0153] [ka]

[0154] Acid generator PAG-1

[0155] [ka]

[0156] Stabilizer DIPEA

[0157] [ka]

[0158] (Preparation of polarizer) A composition for forming a polarizer having the following composition was continuously applied onto the obtained photoalignment film with a wire bar to form a coating film. The coating was then heated at 140° C. for 15 seconds, and the coating was then cooled to room temperature (23° C.). The coating was then heated to 75° C. for 60 seconds and cooled again to room temperature. Then, an LED (light emitting diode) lamp (center wavelength 365 nm) was used to illuminate the specimen at an intensity of 200 mW / cm 2 A polarizer (thickness: 1.8 μm) was prepared on the photo-alignment film by irradiating the polarizer with light for 2 seconds under the irradiation conditions. The transmittance of the polarizer in the wavelength range of 280 to 780 nm was measured using a spectrophotometer, and the average visible light transmittance was 42%. The absorption axis of the polarizer was perpendicular to the width direction of the cellulose acylate film A1.

[0159] ------------------------------------------------------------------ Composition of the polarizer-forming composition ------------------------------------------------------------------ 0.65 parts by weight of the first dichroic material Dye-C1 0.15 parts by weight of the second dichroic material Dye-M1 0.52 parts by weight of the third dichroic material Dey-Y1 2.50 parts by weight of the following liquid crystal compound (L-1) 1.50 parts by weight of the following rod-shaped liquid crystal compound (L-2) Polymerization initiator IRGACUREOXE-02 (BASF) 0.17 parts by mass 0.01 parts by weight of the following surfactant (F-1) Cyclopentanone 92.14 parts by mass Benzyl alcohol 2.36 parts by weight ------------------------------------------------------------------

[0160] Dichroic substance Dye-C1

[0161] [ka]

[0162] Dichroic substance Dye-M1

[0163] [ka]

[0164] Dichroic substance Dye-Y1

[0165] [ka]

[0166] Liquid crystal compound (L-1) (wherein the numerical values ​​("59", "15", "26") described for each repeating unit represent the content (mass%) of each repeating unit relative to the total repeating units.)

[0167] [ka]

[0168] Rod-shaped liquid crystal compound (L-2)

[0169] [ka]

[0170] Surfactant (F-1) (In the formula, the numerical value for each repeating unit indicates the content (mass%) of each repeating unit relative to all repeating units.)

[0171] [ka]

[0172] (Formation of Optically Anisotropic Layer) A composition for forming an optically anisotropic layer containing a rod-shaped liquid crystal compound having the following composition was applied onto the polarizer prepared above, and the resulting composition layer was heated at 60° C. for 100 seconds. The absolute value of the weighted average helical twisting power of the chiral agent in the composition layer was 0.03 μm -1 It was. Then, the sample was exposed to air (oxygen concentration: approximately 20% by volume) at 40°C with an irradiation dose of 52 mJ / cm 2 The composition layer was irradiated with light from a 365 nm LED lamp (manufactured by Acroedge Co., Ltd.) to fix the alignment state of the liquid crystal compound in about half of the region on the polarizer side in the composition layer. The resulting composition layer was then heated at 60° C. for 30 seconds. Thereafter, the film was exposed to light (irradiation dose 500 mJ / cm ) from a metal halide lamp (manufactured by Eye Graphics Co., Ltd.) at 55°C under a nitrogen atmosphere. 2) was irradiated onto the composition layer to fix the liquid crystal compound in half of the region on the air side in the coating film, forming an optically anisotropic layer (thickness: 3.0 μm), and circularly polarizing plate 1 was produced. The optically anisotropic layer was composed of two layers exhibiting different optical anisotropy. The layer on the polarizer side of the optically anisotropic layer (first optically anisotropic layer) was a layer in which rod-shaped liquid crystal compounds were fixed and twisted with the thickness direction as the helical axis, and the molecular axis of the liquid crystal compounds in the layer was parallel to the surface of the optically anisotropic layer. The Δnd of this layer was 282 nm, and the direction of the in-plane slow axis was 0° on the polarizer side surface and -26.5° (twist angle = 26.5°) on the air side surface. In addition, the layer on the air side of the optically anisotropic layer (second optically anisotropic layer) was a layer in which rod-shaped liquid crystal compounds were fixed and twisted with the thickness direction as the helical axis, the molecular axis of the liquid crystal compounds in the layer was parallel to the surface of the optically anisotropic layer, the Δnd of this layer was 140 nm, and the direction of the in-plane slow axis was -26.5° on the polarizer side surface and -105.1° (twist angle = 78.6°) on the air side surface. The above angle is expressed as a positive value in the counterclockwise direction with respect to the absorption axis of the polarizer as the reference (0°) when the optically anisotropic layer is observed from the polarizer side.

[0173] ---------------------------------------------------------------------------------- Composition for forming optically anisotropic layer ---------------------------------------------------------------------------------- The above rod-shaped liquid crystal compound (L-2) 80 parts by mass 10 parts by weight of the following rod-shaped liquid crystal compound (B) 10 parts by mass of the following polymerizable compound (C) Ethylene oxide modified trimethylolpropane triacrylate (V#360, manufactured by Osaka Organic Chemical Co., Ltd.) 4 parts by mass Photopolymerization initiator (Irgacure 819, manufactured by BASF) 3 parts by weight 0.59 parts by mass of the following left-twisted chiral agent (L1) 0.39 parts by mass of the right-twisted chiral agent (R1) shown below 0.08 parts by weight of the following polymer (A) 0.50 parts by weight of the following polymer (B) Methyl isobutyl ketone 121 parts by mass Ethyl propionate 41 parts by mass ----------------------------------------------------------------------------------

[0174] Rod-shaped liquid crystal compound (B)

[0175] [ka]

[0176] Polymerizable compound (C)

[0177] [ka]

[0178] Left-twisted chiral agent (L1)

[0179] [ka]

[0180] Right-twisted chiral agent (R1)

[0181] [ka]

[0182] Polymer (A) (wherein the numerical value for each repeating unit represents the content (mass%) of each repeating unit relative to all repeating units.)

[0183] [ka]

[0184] Polymer (B) (wherein the numerical value for each repeating unit represents the content (mass%) of each repeating unit relative to all repeating units.)

[0185] [ka]

[0186] (Preparation of adhesive layer) Next, an acrylate polymer was prepared according to the following procedure. Butyl acrylate (95 parts by mass) and acrylic acid (5 parts by mass) were polymerized by solution polymerization in a reaction vessel equipped with a cooling tube, a nitrogen inlet tube, a thermometer, and a stirrer, to obtain an acrylate polymer (S1) having an average molecular weight of 2,000,000 and a molecular weight distribution (Mw / Mn) of 3.0.

[0187] Next, the obtained acrylate polymer (S1) was used to obtain a composition for forming a pressure-sensitive adhesive layer having the following composition.

[0188] ------------------------------------------------------------------ Composition for forming adhesive layer ------------------------------------------------------------------ Acrylate polymer (S1) 100 parts by weight 11.1 parts by mass of the following (A) polyfunctional acrylate monomer 1.1 parts by mass of the photopolymerization initiator (B) described below (C) Isocyanate-based crosslinking agent 1.0 part by mass 0.2 parts by mass of the following silane coupling agent (D) ------------------------------------------------------------------

[0189] (A) Multifunctional acrylate monomer: tris(acryloyloxyethyl)isocyanurate, molecular weight = 423, trifunctional type (manufactured by Toagosei Co., Ltd., product name "Aronix M-315") (B) Photopolymerization initiator: A 1:1 mixture of benzophenone and 1-hydroxycyclohexyl phenyl ketone by mass, "Irgacure 500" manufactured by Ciba Specialty Chemicals (C) Isocyanate-based crosslinking agent: Trimethylolpropane-modified tolylene diisocyanate ("Coronate L" manufactured by Nippon Polyurethane Co., Ltd.) (D) Silane coupling agent: 3-glycidoxypropyltrimethoxysilane ("KBM-403" manufactured by Shin-Etsu Chemical Co., Ltd.)

[0190] This adhesive layer-forming composition was applied to a separate film that had been surface-treated with a silicone-based release agent using a die coater, and the resulting coating was dried for 1 minute in an environment of 90° C. Next, the resulting coating was irradiated with ultraviolet (UV) rays under the following conditions to obtain an adhesive layer. The adhesive layer had a thickness of 15 μm. -UV irradiation conditions- Fusion Electrodeless Lamp H Bulb ·Illuminance 600mW / cm 2 , light intensity 150mJ / cm 2 UV illuminance and light intensity were measured using the UVPF-36 made by Eye Graphics.

[0191] A SAMSUNG GALAXY S5 equipped with an organic EL display panel was disassembled, and a touch panel with a circular polarizer was peeled off from the organic EL display device, and the circular polarizer was peeled off from the touch panel to isolate the organic EL display panel, the touch panel, and the circular polarizer. The isolated touch panel was then attached again to the organic EL display panel, and the optically anisotropic layer side of the circular polarizer 1 prepared above was attached to the touch panel via the adhesive layer prepared above, so that air would not enter. The cellulose acylate film A1 of the circular polarizer 1 was then peeled off, and the support side of a low-reflection surface film CV-LC5 (manufactured by FUJIFILM Corporation) was attached to the peeled surface using the adhesive layer prepared above to produce an organic EL display device.

[0192] <Examples 2 to 4, Comparative Example 4> Circular polarizers 2 to 4 and circular polarizer C4 were prepared in the same manner as in Example 1, except that the amounts of the dichroic substances Dye-Y1, Dye-M1, and Dye-C1, the liquid crystal compound (L-1), and the rod-shaped liquid crystal compound (L-2) used in the polarizer-forming composition were changed to the amounts added in parts by mass shown in Table 1, and an organic EL display device was also prepared.

[0193] <Examples 5 to 6> Circularly polarizing plates 5 and 6 were prepared in the same manner as in Example 2, except that the rod-shaped liquid crystal compound (L-2) was changed to the rod-shaped liquid crystal compound (L-3) or the rod-shaped liquid crystal compound (L-4) as shown in Table 1, and further, an organic EL display device was prepared. The rod-shaped liquid crystal compound (L-3) shown in Table 1 below has the following structure.

[0194] [ka]

[0195] The rod-shaped liquid crystal compound (L-4) shown in Table 1 below has the following structure.

[0196] [ka]

[0197] <Examples 7 to 8> Circularly polarizing plate 7 was produced in the same manner as in Example 1, except that the support on which the polarizer-forming composition was applied was changed to a low-reflection surface film CV-LC5 (manufactured by Fujifilm Corporation). In addition, circularly polarizing plate 8 was prepared in the same manner as in Example 1, except that the support on which the polarizer-forming composition was applied was changed to an AR film-attached glass (AR glass 1) formed by bonding an AR film (Dexerials, AR100; 91 μm) and a 50 μm-thick glass substrate (SHOTT, D263) using the adhesive layer prepared above.

[0198] A SAMSUNG GALAXY S5 equipped with an organic EL display panel was disassembled, the touch panel with the circular polarizer was peeled off from the organic EL display device, and the circular polarizer was peeled off from the touch panel to separate the organic EL display panel, the touch panel, and the circular polarizer. The separated touch panel was then reattached to the organic EL display panel, and the optically anisotropic layer sides of the circular polarizers 7 and 8 prepared above were attached to the touch panel via the adhesive layer prepared above, without allowing air to enter, to prepare an organic EL display device.

[0199] <Examples 9 to 11> Circularly polarizing plates 9 to 11 were produced in the same manner as in Example 1, except that the support on which the polarizer-forming composition was applied was changed to a commercially available Cosmoshine SRF (film thickness 80 μm), a commercially available cycloolefin film, or Zeonor ZB12 (film thickness 50 μm) (manufactured by Zeon Corporation).

[0200] A SAMSUNG GALAXY S5 equipped with an organic EL display panel was disassembled, and a touch panel with a circular polarizer was peeled off from the organic EL display device, and the circular polarizer was peeled off from the touch panel to separate the organic EL display panel, the touch panel, and the circular polarizer. The separated touch panel was then attached again to the organic EL display panel, and the optically anisotropic layer sides of the circular polarizers 9 to 11 prepared above were attached to the touch panel via the adhesive layer prepared above, while preventing air from entering. Furthermore, the adhesive layer prepared above was used to attach the support side of a low-reflection surface film CV-LC5 (manufactured by FUJIFILM Corporation) or the glass side of AR glass 1, as shown in Table 1, to prepare an organic EL display device.

[0201] <Comparative Example 1> (Preparation of Cellulose Acylate Film A2) The following components for forming a cellulose acylate dope were charged into a mixing tank and stirred, and the resulting composition was heated at 90° C. for 10 minutes. The obtained composition was then filtered through a filter paper with an average pore size of 34 μm and a sintered metal filter with an average pore size of 10 μm to prepare a dope. The solid content of the dope was 23.5% by mass, the amount of the plasticizer added was the ratio relative to the cellulose acylate, and the solvent of the dope was methylene chloride / methanol / butanol=81 / 18 / 1 (mass ratio).

[0202] ---------------------------------------------------------------------------------- Cellulose Acylate Dope ---------------------------------------------------------------------------------- Cellulose acylate (acetyl substitution degree 2.86, viscosity average polymerization degree 310) 100 parts by mass Sugar ester compound 1 (shown in chemical formula (S4)) 6.0 parts by mass Sugar ester compound 2 (shown in chemical formula (S5)) 2.0 parts by mass Silica particle dispersion (AEROSIL R972, Nippon Aerosil Co., Ltd.) 0.1 part by mass Solvent (methylene chloride / methanol / butanol) ----------------------------------------------------------------------------------

[0203] [ka]

[0204] [ka]

[0205] The dope prepared above was cast using a drum film-forming machine. The dope was cast from a die onto a metal support cooled to 0° C., and then the obtained web (film) was peeled off. The drum was made of SUS.

[0206] The web (film) obtained by casting was peeled off from the drum, and then dried for 20 minutes in a tenter apparatus, which clipped both ends of the web with clips and transported the web at 30 to 40°C during film transport. The web obtained was then post-dried by zone heating while being transported with a roll. The web obtained was knurled and then wound up. The thickness of the obtained cellulose acylate film was 40 μm, the in-plane retardation Re(550) at a wavelength of 550 nm was 1 nm, and the retardation in the thickness direction Rth(550) was 26 nm.

[0207] (Formation of Optically Anisotropic Layer) The cellulose acylate film A2 thus prepared was continuously subjected to a rubbing treatment. At this time, the longitudinal direction of the long film was parallel to the transport direction, and the angle between the longitudinal direction of the film (transport direction) and the rotation axis of the rubbing roller was 90°.

[0208] An optically anisotropic layer was formed on the cellulose acylate film A2 in the same manner as in Example 1, except that the above-mentioned composition for forming an optically anisotropic layer was applied to the rubbed cellulose acylate film A2 using a Giesser coater as a substrate, and an optically anisotropic film was produced.

[0209] Next, the cellulose acylate film A2 side of the optically anisotropic film was attached to the polarizer prepared in Example 1 using the pressure-sensitive adhesive layer prepared above to prepare a circular polarizing plate C1. In the obtained circular polarizing plate C1, the polarizer and the optically anisotropic layer were attached to each other via the pressure-sensitive adhesive layer.

[0210] A SAMSUNG GALAXY S5 equipped with an organic EL display panel was disassembled, and a touch panel with a circular polarizer was peeled off from the organic EL display device, and the circular polarizer was peeled off from the touch panel to separate the organic EL display panel, the touch panel, and the circular polarizer. The separated touch panel was then attached again to the organic EL display panel, and the optically anisotropic layer side of the circular polarizer C1 prepared above was attached to the touch panel via the adhesive layer prepared above, so that air would not enter. Furthermore, the cellulose acylate film A1 of the circular polarizer C1 was peeled off, and the support side of the low-reflection surface film CV-LC5 (manufactured by FUJIFILM Corporation) was attached to the peeled surface using the adhesive layer prepared above to prepare an organic EL display device.

[0211] <Comparative Example 2> The following UV adhesive S1 was prepared. ───────────────────────────────── UV adhesive S1 ------------------------------------------------------------------ CEL2021P (manufactured by Daicel) 70 parts by weight 1,4-butanediol diglycidyl ether 20 parts by weight 2-Ethylhexyl glycidyl ether 10 parts by mass ·CPI-100P 2.25 parts by mass ─────────────────────────────────

[0212] CEL2021P

[0213] [ka]

[0214] CPI-100P

[0215] [ka]

[0216] Using the above UV adhesive S1, the cellulose acylate film A2 side of the optically anisotropic film prepared in Comparative Example 1 was attached to the polarizer prepared in Example 1, and the resulting laminate was exposed to an illuminance of 1000 mJ for curing to prepare a circular polarizing plate C2. In the resulting circular polarizing plate, the polarizer and the optically anisotropic layer were attached to each other via the UV adhesive. Next, an organic EL display device was produced in the same manner as in Comparative Example 1, except that the circular polarizer C2 was used instead of the circular polarizer C1.

[0217] <Comparative Example 3> An alignment film coating solution having the following composition was continuously applied with a wire bar onto the polarizer prepared in Example 1. The resulting coating film was then dried with hot air at 80°C for 5 minutes to obtain a laminate having an alignment film made of polyvinyl alcohol (PVA) having a thickness of 0.5 μm. The resulting laminate has a cellulose acylate film A1 (transparent support), a photoalignment film, a polarizer, and an alignment film made of PVA adjacent to each other in this order. The surface of the laminate on the alignment layer side was continuously subjected to a rubbing treatment. At this time, the longitudinal direction of the long film was parallel to the transport direction, and the angle between the longitudinal direction of the film (transport direction) and the rotation axis of the rubbing roller was 90°. ------------------------------------------------------------------ Alignment film coating solution ------------------------------------------------------------------ 3.80 parts by weight of the following modified polyvinyl alcohol Initiator Irg2959 0.20 parts by weight ·Water 70 parts by mass Methanol 30 parts by weight ------------------------------------------------------------------

[0218] Modified Polyvinyl Alcohol

[0219] [ka]

[0220] The above-mentioned rubbed laminate was used as a substrate, and an optically anisotropic layer was formed on the laminate using a Giesser coater, in the same manner as in Example 1, except that the above-mentioned composition for forming an optically anisotropic layer was applied to the laminate, thereby producing a circular polarizing plate C3. Next, an organic EL display device was produced in the same manner as in Comparative Example 1, except that the circular polarizer C3 was used instead of the circular polarizer C1.

[0221] <Comparative Example 5> A circular polarizing plate C5 comprising a cellulose acylate film, an alignment film, an optically anisotropic layer, and a polarizer layer was prepared by the method described in Example 17 of Japanese Patent No. 5753922.

[0222] A SAMSUNG GALAXY S5 equipped with an organic EL display panel was disassembled, and a touch panel with a circular polarizer was peeled off from the organic EL display device, and the circular polarizer was peeled off from the touch panel to separate the organic EL display panel, the touch panel, and the circular polarizer. The separated touch panel was then attached again to the organic EL display panel, and the support side of the circular polarizer C5 prepared above was attached to the touch panel via the adhesive layer prepared above, without allowing air to enter. Furthermore, the support side of the low-reflection surface film CV-LC5 (manufactured by FUJIFILM Corporation) was attached to the polarizer surface using the adhesive layer prepared above to prepare an organic EL display device.

[0223] When the circular polarizing plates obtained in Examples 1 to 11 were analyzed for components in the depth direction by TOF-SIMS, as shown in Figure 2, a profile (line) indicating the secondary ion intensity originating from the components contained in the polarizer and a profile (line) indicating the secondary ion intensity originating from the components contained in the optically anisotropic layer intersected at a certain depth position. On the other hand, in Comparative Examples 1 to 4, no results were obtained in which the profile (line) showing the secondary ion intensity originating from the components contained in the polarizer and the profile (line) showing the secondary ion intensity originating from the components contained in the optically anisotropic layer intersected, as shown in Figure 2.

[0224] <Durability evaluation> The organic EL display device thus produced was left to stand for 1000 hours in an environment of 95°C and less than 10% relative humidity. After that, the display screen of the organic EL display device thus produced was set to black, and the reflected light was observed when a fluorescent lamp was projected from the front. The display performance was evaluated based on the following criteria. The evaluation results are shown in Table 1 below. <Evaluation criteria> A: Black, no visible coloring, and low reflectance B: Slight coloring is visible, but the reflectance is low C: Slight coloring is visible and the reflectance is high D: Coloring is clearly visible and reflectance is high

[0225] In Table 1, the column "Dichroic material concentration" indicates the content (mass %) of the dichroic material relative to the total mass of the polarizer. The "Laminating Method" column in Table 1 indicates a method for laminating a polarizer and an optically anisotropic layer, and "Laminate Coating" indicates a method for forming an optically anisotropic layer by applying a composition for forming an optically anisotropic layer onto a polarizer so that the polarizer and the optically anisotropic layer are disposed adjacent to each other. "PSA" indicates a method for laminating a polarizer and an optically anisotropic layer via a pressure-sensitive adhesive layer. "UV Adhesion" indicates a method for laminating a polarizer and an optically anisotropic layer via a UV adhesive. "PVA Alignment Film" indicates a method for forming an optically anisotropic layer using a PVA alignment film, and in this form, a PVA alignment film is disposed between the polarizer and the optically anisotropic layer. The "Axial misalignment (°)" column in Table 1 indicates the angle between the absorption axis of the polarizer and the in-plane slow axis of the polarizer-side surface of the optically anisotropic layer (in other words, the in-plane slow axis of the polarizer-side surface of the first optically anisotropic layer). In Table 1, "ΔlogP" represents the absolute value of the difference between the logP of the liquid crystal compound and the logP of the dichroic material. Note that "ΔlogP" represents the smallest absolute value of the difference between the logP of each of the three dichroic materials (Dye-Y1, Dye-M1, Dye-C1) and the logP of the second liquid crystal compound.

[0226] [Table 1]

[0227] [Table 2]

[0228] As shown in Table 1, it was confirmed that the desired effects were obtained when the polarizing plate of the present invention was used. In particular, it was confirmed from Examples 5 and 6 that when ΔloP was 3.0 or more, the effect was more excellent. [Explanation of symbols]

[0229] 10A,10B Polarizing plate 12 Polarizer 14,140 Optically anisotropic layer 16 First optically anisotropic layer 18 Second optically anisotropic layer 20 composition layer 20A 1st area 20B 2nd area

Claims

1. a polarizer formed using a composition including a first liquid crystal compound and a dichroic material; an optically anisotropic layer formed by using a composition containing a second liquid crystal compound and disposed adjacent to the polarizer; A polarizing plate, wherein the content of the dichroic material in the polarizer is 40% by mass or less with respect to the total mass of the polarizer.

2. The polarizing plate according to claim 1 , wherein the content of the dichroic material in the polarizer is 30% by mass or less with respect to the total mass of the polarizer.

3. 3. The polarizing plate according to claim 1, wherein an angle between an absorption axis of the polarizer and an in-plane slow axis of the surface of the optically anisotropic layer facing the polarizer is within 1[deg.].

4. 4. The polarizing plate according to claim 1, wherein the optically anisotropic layer is a layer in which a second liquid crystal compound is fixed and twisted and aligned with a helical axis in the thickness direction.

5. the optically anisotropic layer has a plurality of layers each including a second liquid crystal compound fixed therein and twistedly aligned with a helical axis in a thickness direction; 5. The polarizing plate according to claim 1, wherein the second liquid crystal compound in each of the layers has a different twist angle.

6. the optically anisotropic layer has a plurality of layers each including a second liquid crystal compound fixed therein and twistedly aligned with a helical axis in a thickness direction; 6. The polarizing plate according to claim 1, wherein the plurality of layers each have a different ratio of the twist angle of the second liquid crystal compound to the thickness of the layer.

7. the optically anisotropic layer has a first optically anisotropic layer and a second optically anisotropic layer, the first optically anisotropic layer is disposed on the polarizer side; the first optically anisotropic layer and the second optically anisotropic layer are layers in which the second liquid crystal compound is fixed and twisted in a helical axis along a thickness direction, a twist direction of the second liquid crystal compound in the first optically anisotropic layer is the same as a twist direction of the second liquid crystal compound in the second optically anisotropic layer, the twist angle of the second liquid crystal compound in the first optically anisotropic layer is 26.5±10.0°; the twist angle of the second liquid crystal compound in the second optically anisotropic layer is 78.6±10.0°; an in-plane slow axis of the first optically anisotropic layer at a surface facing the second optically anisotropic layer is parallel to an in-plane slow axis of the second optically anisotropic layer at a surface facing the first optically anisotropic layer, The polarizing plate according to any one of claims 1 to 6, wherein a product Δn1·d1 of a refractive index anisotropy Δn1 of the first optically anisotropic layer measured at a wavelength of 550 nm and a thickness d1 of the first optically anisotropic layer, and a product Δn2·d2 of a refractive index anisotropy Δn2 of the second optically anisotropic layer measured at a wavelength of 550 nm and a thickness d2 of the second optically anisotropic layer, satisfy the following formulas (1) and (2), respectively. Formula (1) 252nm≦Δn1・d1≦312nm Formula (2) 110nm≦Δn2・d2≦170nm

8. The polarizing plate according to any one of claims 1 to 7, wherein, when a component analysis in a depth direction of the polarizer is performed by time-of-flight secondary ion mass spectrometry, a relationship between a maximum intensity Imax of a secondary ion intensity derived from the dichroic material and an intensity Isur1 of a secondary ion intensity derived from the dichroic material on a surface of the polarizer opposite to the optically anisotropic layer side satisfies formula (3). Formula (3) 2.0≦Imax / Isur1

9. 9. The polarizing plate according to claim 1, wherein an absolute value of a difference between the log P of the second liquid crystal compound and the log P of the dichroic material is 3.0 or more.

10. An organic electroluminescence display device comprising the polarizing plate according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Ambient light resistant reflecting film

    CN105807354A

  • Color conversion filter and manufacturing method

    JP2002151262A

  • Retardation plate for circularly polarizing plate, circularly polarizing plate, and organic el (electroluminescence) display device

    JP2014209220A

  • Flexible image display device and method of manufacturing circularly polarizing plate used for the same

    JP2019168691A

  • Polarizer and image display device

    WO2019225468A1